Pulp board for fluff pulp, fluff pad and absorbent article

By adjusting the composition of the pulp board used for fluff pulp, especially the content of hardwood pulp, linear fatty acids, and xylan, the problem of high liquid backflow rate in fluff pads was solved, resulting in fluff pads with low backflow rate and high defiberization properties, suitable for absorbent items such as diapers.

CN120917200APending Publication Date: 2025-11-07OJI HLDG CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202480016823.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-03-06
Filing Date
2024-02-13
Publication Date
2025-11-07

AI Technical Summary

Technical Problem

Existing pulp boards for fluffing pulp have insufficient backflow rate when manufacturing fluff pads, failing to meet the requirement of low backflow rate.

Method used

By adjusting the composition of the fluff pulp board, ensuring that the content of hardwood pulp is above 25% by mass, the total content of straight-chain fatty acids with carbon atoms of 24, 26, and 28 is in the range of 300 to 1000 ppm, controlling the xylan content to below 20% by mass, and optimizing parameters such as ISO brightness, kappa value, and viscosity, a fluff pulp board with high defiberization and low backflow rate is formed.

Benefits of technology

It achieves a low backflow rate for the fluff pad, improves liquid retention and production efficiency, reduces liquid backflow rate, and ensures the appearance and shape stability of the fluff pad, making it suitable for absorbent items such as diapers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005580837390000061
    Figure BDA0005580837390000061
  • Figure BDA0005580837390000101
    Figure BDA0005580837390000101
  • Figure BDA0005580837390000121
    Figure BDA0005580837390000121
Patent Text Reader

Abstract

The present invention addresses the problem of providing a fluff pulp board capable of forming a fluff pulp (fluff pad) in which the liquid backflow rate is sufficiently reduced. The invention relates to a pulp board for fluff pulp, which comprises broad-leaved tree pulp and is described in (A) to (D) below. (A) A fluff pulp board in which the content of broad-leaved tree pulp relative to the total pulp component is 25 mass% or more, and the total content of straight-chain fatty acids having 24, 26, and 28 carbon atoms is 300-1000 ppm. And (B) a fluff pulp board in which the xylan content is 20 mass% or less and the Canadian standard freeness of the dissociated pulp is 400-640 mL. And (C) a fluff pulp board in which the proportion of the number of fibers weighted at a length in the range of 0-0.1 mm in the length-weighted fiber length distribution is 10% or less. And (D) a fluff pulp board in which the fiber roughness measured by dissociating the fluff pulp board is 0.030-0.120 mg / m.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to a fluff pulp sheet, a fluff pad, and an absorbent article. BACKGROUND

[0002] Fluff pulp is made by defibrating wood pulp into a cotton-like form. Fluff pulp is used as a water-absorbing material in absorbent articles such as paper diapers, sanitary napkins, and the like.

[0003] In the past, fluff pulp used in absorbent articles has been made from coniferous pulp that has good defibrating properties (for example, Patent Literature 1). In Patent Literature 1, raw pulp (coniferous bleached kraft pulp) having a moisture content of 35% or less is defibrated by mechanical treatment, thereby obtaining fluff pulp.

[0004] In addition, Patent Literature 2 discloses a fluff pulp sheet containing broadleaf bleached kraft pulp and coniferous bleached kraft pulp. Here, it was investigated that by setting the containing ratio of broadleaf bleached kraft pulp to coniferous bleached kraft pulp to a prescribed range, a fluff pulp sheet that can reduce the backflow of absorbed liquid and suppress the rash of the skin is obtained.

[0005] PRIOR ART DOCUMENTS

[0006] PATENT LITERATURE

[0007] Patent Literature 1: Japanese Patent Application Publication No. 2012-211411

[0008] Patent Literature 2: International Publication No. 2022 / 138870 SUMMARY

[0009] PROBLEMS TO BE SOLVED BY THE INVENTION

[0010] As described above, a fluff pulp sheet containing broadleaf bleached kraft pulp and coniferous bleached kraft pulp is known, but in the conventional fluff pulp sheet, in the case where fluff pulp (fluff pad) is manufactured from the fluff pulp sheet, the backflow rate of liquid is not sufficiently low, and improvement is required.

[0011] Therefore, the present inventors and others have conducted research with the aim of providing a fluff pulp sheet that can form fluff pulp (fluff pad) in which the backflow rate of liquid is sufficiently reduced, in order to solve such problems of the prior art.

[0012] SOLUTION TO PROBLEM

[0013] Examples of specific modes of the present application are shown below.

[0014] [1] A fluff pulp sheet comprising broadleaf pulp,

[0015] The content of the hardwood pulp with respect to the total content of pulp components in the fluff pulp pulp sheet is 25% by mass or more,

[0016] The total content of the straight-chain fatty acid having 24 carbon atoms, the straight-chain fatty acid having 26 carbon atoms, and the straight-chain fatty acid having 28 carbon atoms contained in the fluff pulp pulp sheet is 300 to 1000 ppm.

[0017] [2] The fluff pulp pulp sheet according to [1], which has an ISO brightness of 80% or more as measured in accordance with JIS P 8148:2018.

[0018] [3] The fluff pulp pulp sheet according to [1] or [2], which has a viscosity of 7.0 to 15.0 mPa-s as measured in accordance with JIS P 8215:1998.

[0019] [4] The fluff pulp pulp sheet according to any one of [1] to [3], wherein the kappa number of the hardwood pulp is 0.5 to 2.0.

[0020] [5] The fluff pulp pulp sheet according to any one of [1] to [4], wherein the content of the hardwood pulp with respect to the total content of pulp components in the fluff pulp pulp sheet is 50% by mass or more.

[0021] [6] The fluff pulp pulp sheet according to any one of [1] to [5], which has a kappa number of less than 1.5 as measured in accordance with JIS P 8211:2011.

[0022] [7] A fluff pulp pulp sheet comprising a hardwood pulp,

[0023] The content of xylan contained in the fluff pulp pulp sheet is 20% by mass or less,

[0024] For a disintegrated pulp sheet obtained by disintegrating the fluff pulp pulp sheet in accordance with JIS P 8220-1:2012, when Canadian Standard Freeness (CSF) is measured in accordance with JIS P 8121:2012-2, the Canadian Standard Freeness (CSF) becomes 400 to 640 mL.

[0025] [8] The fluff pulp pulp sheet according to [7], which has an ISO brightness of 82% or more as measured in accordance with JIS P 8148:2018.

[0026] [9] The fluff pulp pulp sheet according to [7] or [8], wherein, in the case where the ISO brightness reduction rate is calculated from the ISO brightness before and after the fluff pulp pulp sheet is heated at 105°C for 72 hours, the ISO brightness is measured in accordance with JIS P 8154-1:2008, and the brightness change amount becomes 5.0% or less.

[0027] Amount of change in ISO whiteness (%) = B0 (%) - B1 (%)

[0028] (Here, B0 represents the ISO whiteness of the pulp board for fluff pulp before the heat treatment, and B1 represents the ISO whiteness of the pulp board for fluff pulp after the heat treatment.)

[0029]

[10] The pulp board for fluff pulp according to any one of [7] to [9], wherein the kappa number of the hardwood pulp is 0.3 to 2.0.

[0030]

[11] The pulp board for fluff pulp according to any one of [7] to

[10] , wherein the content of the hardwood pulp with respect to the entire pulp component in the pulp board for fluff pulp is 25 mass% or more.

[0031]

[12] The pulp board for fluff pulp according to any one of [7] to

[11] , which has a kappa number of less than 1.7 as measured in accordance with JIS P 8211:2011.

[0032]

[13] The pulp board for fluff pulp according to any one of [7] to

[12] , which has a K value of less than 1.6 as measured in accordance with JIS P 8206:1982.

[0033]

[14] A pulp board for fluff pulp, comprising a hardwood pulp,

[0034] For the pulp fibers contained in the pulp board for fluff pulp, the proportion of the number of fibers weighted in the range of 0 to 0.1 mm in length in the length-weighted fiber length distribution is 10% or less when the length-weighted fiber length is measured in accordance with JIS P 8226-2:2011.

[0035]

[15] The pulp board for fluff pulp according to

[14] , which has an ISO whiteness of 82% or more as measured in accordance with JIS P 8148:2018.

[0036]

[16] The pulp board for fluff pulp according to

[14] or

[15] , wherein the kappa number of the hardwood pulp is 0.5 to 2.0.

[0037]

[17] The pulp board for fluff pulp according to any one of

[14] to

[16] , which has a kappa number of less than 1.7 as measured in accordance with JIS P 8211:2011.

[0038]

[18] The pulp board for fluff pulp according to any one of

[14] to

[17] , wherein the content of the hardwood pulp with respect to the entire pulp component in the pulp board for fluff pulp is 25 mass% or more.

[0039]

[19] A fluff pulp slurry board comprising a hardwood pulp,

[0040] The fiber coarseness measured by disintegrating the fluff pulp slurry board according to JIS P 8220-1:2012 is 0.030 to 0.120 mg / m.

[0041]

[20] The fluff pulp slurry board according to

[19] , wherein the length-weighted average fiber length of the pulp fibers contained in the fluff pulp slurry board, measured according to JIS P 8226-2:2011, is 0.65 mm or more and less than 1.50 mm.

[0042]

[21] The fluff pulp slurry board according to

[19] or

[20] , which has an ISO brightness measured according to JIS P 8148:2018 of 82% or more.

[0043]

[22] The fluff pulp slurry board according to any one of

[19] to

[21] , wherein the kappa value of the hardwood pulp is 0.5 to 2.0.

[0044]

[23] The fluff pulp slurry board according to any one of

[19] to

[22] , wherein the content of the hardwood pulp with respect to the total pulp components in the fluff pulp slurry board is 25 mass% or more.

[0045]

[24] The fluff pulp slurry board according to any one of

[19] to

[23] , which has a kappa value measured according to JIS P 8211:2011 of less than 1.7.

[0046]

[25] A fluff mat formed from the fluff pulp slurry board according to any one of [1] to

[24] .

[0047]

[26] The fluff mat according to

[25] , which has a density of 0.058 g / cm 3 or more.

[0048]

[27] An absorbent article provided with the fluff mat according to

[25] or

[26] .

[0049] Effects of the Invention

[0050] According to the present invention, a fluff mat having a reduced backflow rate can be obtained. BRIEF DESCRIPTION OF DRAWINGS

[0051] Figure 1 is a schematic view illustrating the configuration of a fluff mat manufacturing device for manufacturing a fluff mat. DETAILED DESCRIPTION

[0052] The present application will be described in detail below. The description of the technical features described below is sometimes made based on representative embodiments, specific examples, but the present application is not limited to such embodiments. Note that the numerical range represented by "~" in this specification means a range including the numerical values described before and after "~" as lower limit values and upper limit values.

[0053] (Slurry board for fluff pulp)

[0054] (First Embodiment)

[0055] The first embodiment relates to a slurry board for fluff pulp, which contains hardwood pulp, wherein the content of the hardwood pulp with respect to the total pulp component in the slurry board for fluff pulp is 25 mass% or more, and the total content of linear fatty acid having 24 carbon atoms, linear fatty acid having 26 carbon atoms, and linear fatty acid having 28 carbon atoms contained in the slurry board for fluff pulp is 300 to 1000 ppm. Note that, in this specification, "fluff pulp" means a pulp after defibration, and a pulp which has been fiberized or cut. In addition, "slurry board for fluff pulp" means a pulp before defibration, which is used for manufacturing fluff pulp. That is, "fluff pulp" is obtained by defibrating "slurry board for fluff pulp", and a substance obtained by forming "fluff pulp" into a sheet shape is called "fluff mat". In this specification, "slurry board for fluff pulp" is obtained, for example, by papermaking a slurry containing a prescribed raw pulp.

[0056] In the first embodiment, the total content of linear fatty acid having 24 carbon atoms, linear fatty acid having 26 carbon atoms, and linear fatty acid having 28 carbon atoms contained in the slurry board for fluff pulp is preferably 300 ppm or more, more preferably 320 ppm or more, and further preferably 350 ppm or more. In addition, the total content of linear fatty acid having 24 carbon atoms, linear fatty acid having 26 carbon atoms, and linear fatty acid having 28 carbon atoms contained in the slurry board for fluff pulp is preferably 1000 ppm or less, more preferably 990 ppm or less, and further preferably 980 ppm or less.

[0057] The total content of the straight-chain fatty acid having 24 carbon atoms, the straight-chain fatty acid having 26 carbon atoms, and the straight-chain fatty acid having 28 carbon atoms contained in the fluff pulp board is calculated by the following method. First, the fluff pulp board is dried, and about 200 mg of the dried pulp is accurately weighed, 0.1 ml of concentrated hydrochloric acid (12 equivalents) and 2 ml of chloroform are added, and ultrasonic treatment is performed for 10 minutes. The obtained extract is filtered with a membrane filter (pore size 0.2 μm), and the filtrate is analyzed by high-performance liquid chromatography. As the eluent, methanol: acetone containing 0.1 mass% of trifluoroacetic acid = 50:50 is used, and the flow rate of the high-performance liquid chromatography is set to 1 ml / min. As the column used, for example, X Bridge C18, 250 mm x 4.6 mm I.D. manufactured by Waters Inc. can be used. The temperature at the time of analysis is 30°C, and 2 μl of the filtrate is injected. The detector uses a charged particle detector, and the straight-chain fatty acid (higher fatty acid: C 23 H 47 COOH, C 25 H 51 COOH, C 27 H 55 COOH) is calculated by the following calculation formula, and the total concentration is calculated. The peak area value of each component can be calculated as follows: for the peaks that are the portions surrounded by the baseline and each peak but partially repeated, the peak separation can be performed by the perpendicular method of JIS K 0124:2011 to calculate.

[0058] In the first embodiment, for example, by appropriately adjusting the raw material of the pulp, the manufacturing conditions of the pulp, and the papermaking conditions of the fluff pulp board, it is possible to control the total content of the straight-chain fatty acid having 24 carbon atoms, the straight-chain fatty acid having 26 carbon atoms, and the straight-chain fatty acid having 28 carbon atoms contained in the fluff pulp board within the above range.

[0059] In the first embodiment, by making the total content of the straight-chain fatty acid having 24 carbon atoms, the straight-chain fatty acid having 26 carbon atoms, and the straight-chain fatty acid having 28 carbon atoms contained in the fluff pulp within a prescribed range, a fluff pulp board having a good appearance in which the occurrence of dust is suppressed can be obtained. Here, the appearance of the fluff pulp board is determined to be good in the case where the number of dusts (inclusions) observed per 100 g of the fluff pulp board is small. Specifically, the number of dusts (inclusions) observed per 100 g of the fluff pulp board is preferably 19 or less, more preferably 15 or less, further preferably 10 or less, and particularly preferably 8 or less. Note that the number of dusts (inclusions) observed per 100 g of the fluff pulp board is most preferably 0. The straight-chain fatty acid contained in the pulp originates from the pulp raw material and is slowly aggregated in the manufacturing process of the pulp to grow to the size of dust, and thus it is considered that the smaller the total content of the straight-chain fatty acids described above, the smaller the number of dusts.

[0060] In addition, in the first embodiment, by making the content of the hardwood pulp with respect to the total content of the pulp component in the fluff pulp board be a prescribed amount or more, and further making the total content of the straight-chain fatty acid having 24 carbon atoms, the straight-chain fatty acid having 26 carbon atoms, and the straight-chain fatty acid having 28 carbon atoms contained in the fluff pulp board be within a prescribed range, the backflow rate of liquid can be reduced when a fluff pad is formed from the fluff pulp board. It is considered that by making the total content of the straight-chain fatty acids described above be the lower limit value or more, the damage to the pulp fiber can be reduced, and the liquid retention can be improved.

[0061] The backflow rate of liquid in the fluff pad can be calculated by the following equation. Here, the backflow rate of liquid in the fluff pad can be calculated as follows: after the fluff pad absorbs 20 g of artificial urine, 10 sheets of filter paper (manufactured by ADVANTEC Corporation, No. 1640) are pressed and placed under the conditions described in the examples, and the weight of the liquid absorbed by the filter paper at that time is measured, and thus the backflow rate is calculated.

[0062]

[0063] Specifically, the backflow rate of liquid in the fluff pad is preferably less than 81%, more preferably 80% or less, further preferably 79% or less, and particularly preferably 75% or less.

[0064] Further, since the pulp sheet for fluff pulp of the first embodiment has the above-described configuration, the defibrating property at the time of fluffing is good. In the present specification, the defibrating property can be evaluated in terms of the defibrating time (seconds) required until the un-defibrated material disappears. Specifically, the shorter the defibrating time, the better the defibrating property can be judged to be, and if the defibrating property is good, the production efficiency of the fluff mat can be improved. Further, if the defibrating property is good, it becomes easy to obtain a fluff mat in which the backflow rate of the liquid is further reduced. Further, if the defibrating property is good, since the amount of un-defibrated material in the fluff mat is reduced, not only the appearance of the fluff mat is optimized, but also the ability of the fluff mat to maintain the shape is improved, and when used as an absorption layer of a sanitary material such as a paper diaper, the possibility of the absorption performance of the paper diaper being reduced due to the shape of the absorption layer being destroyed by the movement in use can be reduced.

[0065] In the pulp sheet for fluff pulp of the first embodiment, the ISO whiteness measured in accordance with JIS P 8148:2018 is preferably 80% or more, more preferably 81% or more, further preferably 82% or more, and particularly preferably 83% or more. In addition, the ISO whiteness of the pulp sheet for fluff pulp is preferably 93% or less. By making the ISO whiteness of the pulp sheet for fluff pulp within the above-described range, a pulp sheet for fluff pulp having a more excellent appearance can be obtained. In addition, by making the ISO whiteness of the pulp sheet for fluff pulp within the above-described range, a fluff mat having a high whiteness can be obtained.

[0066] For the pulp sheet for fluff pulp of the first embodiment, the viscosity measured in accordance with JIS P 8215:1998 is preferably 7.0 mPa-s or more, more preferably 7.5 mPa-s or more, further preferably 8.0 mPa-s or more, more further preferably 8.2 mPa-s or more, and particularly preferably 8.4 mPa-s or more. In addition, for the pulp sheet for fluff pulp, the viscosity measured in accordance with JIS P 8215:1998 is preferably 15.0 mPa-s or less, more preferably 14.7 mPa-s or less, and further preferably 14.5 mPa-s or less. In addition, when measuring the viscosity of the pulp sheet for fluff pulp, the measurement of the viscosity is performed after obtaining the viscosity measurement solution under the conditions described in JIS P 8215:1998. By making the viscosity measured for the pulp sheet for fluff pulp within the above-described range, a pulp sheet for fluff pulp having a more excellent defibrating property can be obtained.

[0067] In the pulp sheet for fluff pulp of the first embodiment, the kappa value measured in accordance with JIS P 8211:2011 is preferably less than 1.5, more preferably 1.4 or less, and further preferably 1.3 or less. The lower limit value of the kappa value of the pulp sheet for fluff pulp is not particularly limited, and is, for example, preferably 0.1 or more. By making the kappa value of the pulp sheet for fluff pulp within the above-described range, a pulp sheet for fluff pulp having a high whiteness and a more excellent defibrating property can be obtained.

[0068] The basis weight of the pulp sheet for fluff pulp of the first embodiment is not particularly limited, and is preferably 100 g / m 2 More preferably, the basis weight of the pulp sheet for fluff pulp is 150 g / m 2 Further preferably, the basis weight of the pulp sheet for fluff pulp is 200 g / m 2 More preferably, the basis weight of the pulp sheet for fluff pulp is 250 g / m 2 Further preferably, the basis weight of the pulp sheet for fluff pulp is 300 g / m 2 More preferably, the basis weight of the pulp sheet for fluff pulp is 350 g / m 2 Further preferably, the basis weight of the pulp sheet for fluff pulp is 400 g / m The basis weight of the pulp sheet for fluff pulp is measured in accordance with JIS P 8124:2011.

[0069] The density of the pulp sheet for fluff pulp of the first embodiment is not particularly limited, and is preferably 0.3 g / cm 3 More preferably, the density of the pulp sheet for fluff pulp is 0.4 g / cm 3 Further preferably, the density of the pulp sheet for fluff pulp is 0.5 g / cm 3 More preferably, the density of the pulp sheet for fluff pulp is 0.6 g / cm 3 Further preferably, the density of the pulp sheet for fluff pulp is 0.7 g / cm 3 More preferably, the density of the pulp sheet for fluff pulp is 0.8 g / cm 3 Further preferably, the density of the pulp sheet for fluff pulp is 0.9 g / cm The density of the pulp sheet for fluff pulp is measured in accordance with JIS P 8118:2014.

[0070] The burst index of the pulp sheet for fluff pulp of the first embodiment measured in accordance with JIS P 8131:2009 is preferably 0.5 kPa·m 2 More preferably, the burst index of the pulp sheet for fluff pulp is 0.7 kPa·m 2 Further preferably, the burst index of the pulp sheet for fluff pulp is 0.9 kPa·m 2 More preferably, the burst index of the pulp sheet for fluff pulp is 1.1 kPa·m 2 Further preferably, the burst index of the pulp sheet for fluff pulp is 1.3 kPa·m 2 More preferably, the burst index of the pulp sheet for fluff pulp is 1.5 kPa·m 2 Further preferably, the burst index of the pulp sheet for fluff pulp is 1.7 kPa·m

[0071] <Second Embodiment>

[0072] The second embodiment relates to a pulp sheet for fluff pulp, which contains deciduous tree pulp, wherein the content of xylan contained in the pulp sheet for fluff pulp is 20 mass% or less, and, for a disintegrated pulp obtained by disintegrating the pulp sheet for fluff pulp in accordance with JIS P 8220-1:2012, Canadian Standard Freeness (CSF) is 400 to 640 mL when measured in accordance with JIS P 8121:2012-2.

[0073] In the second embodiment, the content of xylan contained in the pulp sheet for fluff pulp is preferably 20 mass% or less, more preferably 18 mass% or less, and further preferably 17 mass% or less. The lower limit of the content of xylan contained in the pulp sheet for fluff pulp is not particularly limited and can be 0 mass%.

[0074] The content of xylan contained in the pulp sheet for fluff pulp is calculated from the result of quantitative analysis of xylan contained in the pulp sheet for fluff pulp using the following equation. Note that the quantitative analysis of xylan can be performed by subjecting the pulp sheet for fluff pulp to acid hydrolysis using sulfuric acid and then performing ion chromatography in accordance with NREL / TP-510-42618.

[0075] Xylan amount (g) = xylan measurement amount (μM) x 132 (molecular weight of xylan unit) / over-degradation rate of acid-based sugars (%)

[0076] Xylan amount (%) = xylan amount (g) / mass of pulp sheet for fluff pulp supplied to ion chromatography (g)

[0077] In the second embodiment, for a disintegrated pulp obtained by disintegrating the pulp sheet for fluff pulp in accordance with JIS P 8220-1:2012, Canadian Standard Freeness (CSF) is preferably 400 mL or more, more preferably 420 mL or more, and further preferably 450 mL or more, when measured in accordance with JIS P 8121:2012-2. In addition, the above Canadian Standard Freeness (CSF) is preferably 640 mL or less, more preferably 620 mL or less, and further preferably 600 mL or less.

[0078] In the second embodiment, for example, by appropriately adjusting the raw material of the pulp or the manufacturing conditions of the pulp, the sheet formation conditions of the pulp sheet for fluff pulp, and the beating conditions, it is possible to control the content of xylan contained in the pulp sheet for fluff pulp within the above range, and further to control the above Canadian Standard Freeness (CSF) within the prescribed range.

[0079] In the second embodiment, by making the content of xylan contained in the fluff pulp within a prescribed range, and further making the Canadian Standard Freeness (CSF) of the disintegrated pulp within a prescribed range, it is possible to obtain a fluff pulp having good defibrability. In the present specification, defibrability can be evaluated in terms of the defibrating time (seconds) required until the un-defibrated matter disappears. Specifically, the shorter the defibrating time, the better the defibrability can be judged to be, and if the defibrability is good, it is possible to improve the production efficiency of the fluff mat. Further, if the defibrability is good, it becomes easy to obtain a fluff mat in which the rate of backflow of liquid is further reduced. Further, if the defibrability is good, the amount of un-defibrated matter in the fluff mat is reduced, and thus not only the appearance of the fluff mat is optimized, but also the ability of the fluff mat to maintain its shape is improved, and thus when used as an absorbent layer of a sanitary material such as a paper diaper, it is possible to reduce the possibility that the shape of the absorbent layer is destroyed due to movement during use, and thus the absorbency of the paper diaper is reduced.

[0080] Further, in the second embodiment, by making the content of xylan contained in the fluff pulp within a prescribed range, and further making the Canadian Standard Freeness (CSF) of the disintegrated pulp within a prescribed range, it is possible to reduce the rate of backflow of liquid when a fluff mat is formed from the fluff pulp.

[0081] In the second embodiment, it is considered that by making the content of xylan within a prescribed range, it is possible to reduce the strength of chemical bonding between pulp fibers, and to make the defibrability good. Further, it is considered that by making the Canadian Standard Freeness (CSF) within a prescribed range, it is possible to weaken the degree of entanglement or hydrogen bonding between pulp fibers in the fluff pulp, to improve the defibrability, and by improving the water retention of the pulp fibers, it is possible to reduce the rate of backflow of liquid in the fluff mat.

[0082] The rate of backflow of liquid in the fluff mat can be calculated by the following formula. Here, the rate of backflow of liquid in the fluff mat can be calculated as follows: after the fluff mat has absorbed 20 g of artificial urine, 10 sheets of filter paper (manufactured by ADVANTEC Corporation, No. 1640) are pressed and placed under the conditions described in the examples, and the weight of the liquid absorbed by the filter paper at that time is measured, and thus the rate of backflow of liquid is calculated.

[0083]

[0084] Specifically, the rate of backflow of liquid in the fluff mat is preferably 85% or less, more preferably 82% or less, further preferably 80% or less, and particularly preferably 79% or less.

[0085] Further, in the second embodiment, by making the content of xylan contained in the pulp sheet for fluff pulp be within a prescribed range, and further making the Canadian Standard Freeness (CSF) of the disintegrated pulp be within a prescribed range, a pulp sheet for fluff pulp that is excellent in appearance and inhibits discoloration can be obtained. In the present specification, the inhibition of discoloration can be evaluated by the amount of change in ISO brightness before and after heat treatment. Specifically, the pulp sheet for fluff pulp is heat treated at 105°C for 72 hours in accordance with JIS P 8154-1:2008, and the ISO brightness before and after heat treatment is measured in accordance with JIS P 8148:2018. Further, the amount of change in ISO brightness is calculated by the following formula.

[0086] Amount of change in ISO brightness (%) = B0 (%) - B1 (%)

[0087] Here, B0 represents the ISO brightness of the pulp sheet for fluff pulp before heat treatment, and B1 represents the ISO brightness of the pulp sheet for fluff pulp after heat treatment.

[0088] In the second embodiment, the amount of change in ISO brightness is preferably 5.0% or less, more preferably 4.8% or less, further preferably 4.6% or less, more further preferably 4.4% or less, and particularly preferably 4.2% or less. If the amount of change in ISO brightness is within the above range, it can be evaluated as a pulp sheet for fluff pulp that is excellent in appearance and inhibits discoloration.

[0089] In the pulp sheet for fluff pulp of the second embodiment, the ISO brightness (ISO brightness before heating) measured in accordance with JIS P 8148:2018 is preferably 80% or more, more preferably 81% or more, further preferably 82% or more, and particularly preferably 83% or more. In addition, the ISO brightness of the pulp sheet for fluff pulp is preferably 93% or less. By making the ISO brightness of the pulp sheet for fluff pulp be within the above range, a pulp sheet for fluff pulp that is more excellent in appearance can be obtained. In addition, by making the ISO brightness of the pulp sheet for fluff pulp be within the above range, a fluff pad that is high in brightness can be obtained.

[0090] In the pulp sheet for fluff pulp of the second embodiment, the kappa value measured in accordance with JIS P 8211:2011 is preferably less than 1.7, more preferably less than 1.6, further preferably 1.5 or less, and particularly preferably 1.4 or less. The lower limit value of the kappa value of the pulp sheet for fluff pulp is not particularly limited, and is, for example, preferably 0.1 or more. By making the kappa value of the pulp sheet for fluff pulp be within the above range, a pulp sheet for fluff pulp that is high in brightness and more excellent in defibrating property can be obtained.

[0091] In the pulp sheet for fluff pulp of the second embodiment, the K value measured in accordance with JIS P 8206:1982 is preferably less than 1.6, more preferably 1.5 or less, and further preferably 1.4 or less. The lower limit value of the K value of the pulp sheet for fluff pulp is not particularly limited, and is preferably 0.1 or more, for example. By setting the K value of the pulp sheet for fluff pulp within the above range, a pulp sheet for fluff pulp having a higher degree of defibration and a higher degree of whiteness can be obtained.

[0092] The preferred ranges of the basis weight, the density, and the burst index measured in accordance with JIS P 8131:2009 of the pulp sheet for fluff pulp of the second embodiment are the same as those of the pulp sheet for fluff pulp of the first embodiment.

[0093] <Third Embodiment>

[0094] The third embodiment relates to a pulp sheet for fluff pulp, which contains hardwood pulp, and in which, with respect to the pulp fibers contained in the pulp sheet for fluff pulp, the proportion of the number of fibers having a length-weighted fiber length of 0.1 mm or less in the distribution of the length-weighted fiber length, to the total number of the pulp fibers contained in the pulp sheet for fluff pulp, is 10% or less.

[0095] In the present specification, with respect to the pulp fibers contained in the pulp sheet for fluff pulp, the proportion of the number of fibers having a length-weighted fiber length of 0.1 mm or less in the distribution of the length-weighted fiber length, to the total number of the pulp fibers contained in the pulp sheet for fluff pulp, is also referred to as the amount of fine fibers (%). The amount of fine fibers (%) in the pulp sheet for fluff pulp is preferably 10% or less, more preferably 9.5% or less, and further preferably 9.0% or less. The lower limit value of the amount of fine fibers (%) in the pulp sheet for fluff pulp is not particularly limited, and can be 0%.

[0096] Here, the measurement of the length-weighted fiber length of the pulp fibers contained in the pulp sheet for fluff pulp is performed in accordance with JIS P 8226-2:2011. The length-weighted fiber length of the pulp fibers is the disintegrated fiber length of the pulp fibers, and therefore, the measurement of the length-weighted fiber length is performed on the disintegrated pulp fibers in accordance with JIS P 8226-2:2011. Then, the proportion of the number of fibers having a length of 0 to 0.1 mm in the distribution of the obtained length-weighted fiber length, to the total number of the fibers, is calculated as the amount of fine fibers.

[0097] In the third embodiment, for example, by appropriately adjusting the manufacturing conditions of the pulp sheet for fluff pulp, the kind of pulp used, the presence or absence of a classification process of the pulp fibers, and the classification conditions, the amount of fine fibers contained in the pulp sheet for fluff pulp can be controlled within the above range.

[0098] In the third embodiment, by making the amount of fine fibers contained in the pulp sheet for fluff pulp be within a prescribed range, a pulp sheet for fluff pulp with good defibrillation can be obtained. In the present specification, defibrillation can be evaluated in terms of the defibrillation time (seconds) required until the un-defibrated material disappears. Specifically, the shorter the defibrillation time, the better the defibrillation can be judged to be, and if the defibrillation is good, the production efficiency of the fluff mat can be improved. Further, if the defibrillation is good, it becomes easy to obtain a fluff mat in which the rate of backflow of liquid is further reduced. Furthermore, if the defibrillation is good, the amount of un-defibrated material in the fluff mat is reduced, so not only is the appearance of the fluff mat optimized, but also the ability of the fluff mat to maintain its shape is improved, so when used as an absorbent layer of a sanitary material such as a paper diaper, the possibility of the shape of the absorbent layer being destroyed by movement during use and thus the absorbency of the paper diaper being reduced can be reduced.

[0099] Further, in the third embodiment, by making the amount of fine fibers contained in the pulp sheet for fluff pulp be within a prescribed range, when a fluff mat is formed from the pulp sheet for fluff pulp, the rate of backflow of liquid can be reduced.

[0100] The rate of backflow of liquid in the fluff mat can be calculated by the following formula. Here, the rate of backflow of liquid in the fluff mat can be calculated as follows: after the fluff mat has absorbed 20 g of artificial urine, 10 sheets of filter paper (manufactured by ADVANTEC, No. 1640) are pressed and placed under the conditions described in the examples, the weight of the liquid absorbed by the filter paper is measured, and thus the rate of backflow of liquid can be calculated.

[0101]

[0102] Specifically, the rate of backflow of liquid in the fluff mat is preferably 85% or less, more preferably 82% or less, further preferably 80% or less, and particularly preferably 79% or less.

[0103] Further, in the third embodiment, the rate of backflow can also be reduced in a diaper provided with a fluff mat. The rate of backflow of liquid in the diaper can be calculated according to the following formula. Specifically, the rate of backflow of liquid in a fluff mat (a simulated diaper) in which a highly water-absorbent polymer has been uniformly spread can be calculated as follows: after the fluff mat has absorbed 20 g of artificial urine, 10 sheets of filter paper (manufactured by ADVANTEC, No. 1640) are pressed and placed under the conditions described in the examples, the weight of the liquid absorbed by the filter paper is measured, and thus the rate of backflow of liquid can be calculated.

[0104]

[0105] Specifically, the rate of backflow of liquid in the diaper is preferably 20% or less, more preferably 15% or less, and further preferably 10% or less.

[0106] If the amount of fine fibers contained in the fluff pulp sheet is increased, the water retention property is improved, and thus the backflow rate of liquid when the fluff pad absorbs liquid and pressure is applied is reduced. In addition, if the amount of fine fibers contained in the fluff pulp sheet is reduced, the size of the pores in the fluff pulp sheet becomes large, and thus the fibrillation property is improved. In this way, in the third embodiment, by making the amount of fine fibers be within a prescribed range, it is possible to balance the backflow rate and the fibrillation property.

[0107] In the fluff pulp sheet of the third embodiment, the ISO whiteness measured in accordance with JIS P 8148:2018 is preferably 80% or greater, more preferably 81% or greater, further preferably 82% or greater, and particularly preferably 83% or greater. In addition, the ISO whiteness of the fluff pulp sheet is preferably 93% or less. By making the ISO whiteness of the fluff pulp sheet be within the above range, it is possible to obtain a fluff pulp sheet that has a more excellent appearance. In addition, by making the ISO whiteness of the fluff pulp sheet be within the above range, it is possible to obtain a fluff pad that has a high whiteness.

[0108] In the fluff pulp sheet of the third embodiment, the kappa value measured in accordance with JIS P 8211:2011 is preferably less than 1.7, more preferably less than 1.6, further preferably 1.5 or less, more further preferably less than 1.5, and particularly preferably 1.4 or less. The lower limit value of the kappa value of the fluff pulp sheet is not particularly limited, and is, for example, preferably 0.1 or greater. By making the kappa value of the fluff pulp sheet be within the above range, it is possible to obtain a fluff pulp sheet that has a high whiteness and a more excellent fibrillation property.

[0109] The preferred numerical ranges of the basis weight, the density, and the burst index resistance measured in accordance with JIS P 8131:2009 of the fluff pulp sheet of the third embodiment are the same as those of the fluff pulp sheet of the first embodiment.

[0110] <Fourth Embodiment>

[0111] The fourth embodiment relates to a fluff pulp sheet including a hardwood pulp, the fiber coarseness measured by disintegrating the fluff pulp sheet in accordance with JIS P 8220-1:2012 being 0.03 to 0.12 mg / m.

[0112] In the present embodiment, the fiber coarseness measured by disintegrating the fluff pulp sheet in accordance with JIS P 8220-1:2012 is preferably 0.030 mg / m or greater, more preferably 0.035 mg / m or greater, and further preferably 0.040 mg / m or greater. In addition, the fiber coarseness measured by disintegrating the fluff pulp sheet is preferably 0.120 mg / m or less, and more preferably 0.110 mg / m or less.

[0113] In the present embodiment, for example, by appropriately adjusting the raw material of the pulp, the manufacturing conditions of the pulp, and the sheet formation conditions of the pulp sheet for fluff pulp, it is possible to control the fiber coarseness measured by dissociating the pulp sheet for fluff pulp to be within the above range.

[0114] In the present embodiment, by making the fiber coarseness measured by dissociating the pulp sheet for fluff pulp to be within a prescribed range, it is possible to obtain a fluff pad having a large density, as a result of which it is possible to form a fluff pad having a small thickness. Specifically, the density of the obtained fluff pad is preferably 0.058 g / cm 3 More preferably, 0.060 g / cm 3 or more. Note that the density of the obtained fluff pad is preferably 0.150 g / cm 3 or more.

[0115] In addition, in the present embodiment, by making the fiber coarseness measured by dissociating the pulp sheet for fluff pulp to be within a prescribed range, it is possible to reduce the backflow rate of liquid when forming a fluff pad from the pulp sheet for fluff pulp.

[0116] The backflow rate of liquid in the fluff pad can be calculated according to the following formula. Here, the backflow rate of liquid in the fluff pad can be calculated as follows: after causing the fluff pad to absorb 20 g of artificial urine, 10 sheets of filter paper (manufactured by ADVANTEC Corporation, No. 1640) are placed under pressure in the conditions described in the examples, and the weight of the liquid absorbed by the filter paper at that time is measured, thereby calculating the backflow rate.

[0117]

[0118] Specifically, the backflow rate of liquid in the fluff pad is preferably 85% or less, more preferably 82% or less, further preferably 80% or less, and particularly preferably 79% or less.

[0119] The fiber coarseness is an index related to the rigidity of the pulp fibers, and by reducing the fiber coarseness of the pulp fibers contained in the pulp sheet for fluff pulp, the size of the pores in the fluff pad becomes smaller. Therefore, the density of the fluff pad becomes larger. In addition, since the capillary phenomenon becomes easier to act, it can be considered that the ability to retain liquid in the pores in the fluff pad is improved, and it is possible to reduce the backflow rate of liquid.

[0120] The length-weighted average fiber length of the pulp fibers contained in the pulp sheet for fluff pulp of the present embodiment, measured according to JIS P 8226-2:2011, is preferably 0.65 mm or more, and more preferably 0.70 mm or more. In addition, the length-weighted average fiber length of the pulp fibers contained in the pulp sheet for fluff pulp, measured according to JIS P 8226-2:2011, is preferably less than 1.50 mm, more preferably 1.45 mm or less, and further preferably 1.40 mm or less.

[0121] Here, the length-weighted average fiber length of the pulp fibers contained in the fluff pulp slurry board is measured in accordance with JIS P 8226-2:2011. The length-weighted fiber length of the pulp fibers is the disintegrated fiber length of the pulp fibers, and thus the measurement of the length-weighted average fiber length is performed on the disintegrated pulp fibers in accordance with JIS P 8226-2:2011.

[0122] In the present embodiment, by making the length-weighted average fiber length of the pulp fibers contained in the fluff pulp slurry board be within a prescribed range, it becomes easier to obtain a fluff mat having a large density, and as a result, it becomes easier to form a fluff mat having a thin thickness. In addition, in the present embodiment, by making the length-weighted average fiber length of the pulp fibers contained in the fluff pulp slurry board be within a prescribed range, it is possible to more effectively reduce the backflow rate of the liquid when forming a fluff mat from the fluff pulp slurry board.

[0123] In the fluff pulp slurry board of the present embodiment, the ISO brightness measured in accordance with JIS P 8148:2018 is preferably 80% or greater, more preferably 81% or greater, further preferably 82% or greater, and particularly preferably 83% or greater. In addition, the ISO brightness of the fluff pulp slurry board is preferably 93% or less. By making the ISO brightness of the fluff pulp slurry board be within the above range, it is possible to obtain a fluff pulp slurry board having a more excellent appearance. In addition, by making the ISO brightness of the fluff pulp slurry board be within the above range, it is possible to obtain a fluff mat having a high brightness.

[0124] In the fluff pulp slurry board of the present embodiment, the kappa value measured in accordance with JIS P 8211:2011 is preferably less than 1.7, more preferably less than 1.6, further preferably 1.5 or less, and particularly preferably 1.4 or less. The lower limit value of the kappa value of the fluff pulp slurry board is not particularly limited, and is preferably, for example, 0.1 or greater. By making the kappa value of the fluff pulp slurry board be within the above range, it is possible to obtain a fluff pulp slurry board having a high brightness and more excellent defibrating properties.

[0125] The preferred numerical ranges of the basis weight, the density, and the burst index resistance measured in accordance with JIS P 8131:2009 of the fluff pulp slurry board of the fourth embodiment are the same as those of the fluff pulp slurry board of the first embodiment.

[0126] (Pulp)

[0127] The pulp sheet for fluff pulp of the present embodiment (hereinafter, the first to fourth embodiments will be collectively referred to as the present embodiment) contains hardwood pulp. The hardwood pulp is preferably hardwood bleached kraft pulp. The raw material of the hardwood bleached kraft pulp preferably contains at least one selected from the group consisting of Acacia, Eucalyptus, Quercus, Cyclobalanopsis, and Pinus, and more preferably contains at least one selected from the group consisting of Acacia and Eucalyptus. In addition, in the present embodiment, it is preferable to use Acacia and Eucalyptus together as the raw material of the hardwood bleached kraft pulp. In particular, by causing the pulp sheet for fluff pulp to contain the hardwood bleached kraft pulp manufactured from Acacia, it is possible to more effectively improve the liquid absorbency of the fluff pad and more effectively reduce the liquid backflow rate when the pulp sheet for fluff pulp is fluffed. Note that the raw material of the hardwood bleached kraft pulp can be appropriately used from the above-described raw materials, and in particular, in the second embodiment, it is preferable to control the compounding amount in accordance with the content of xylan contained in each raw material.

[0128] The content of the hardwood pulp with respect to the entire pulp component in the pulp sheet for fluff pulp is preferably 25% by mass or more, more preferably 30% by mass or more, further preferably 35% by mass or more, more further preferably 40% by mass or more, still further preferably 45% by mass or more, and particularly preferably 50% by mass or more. The upper limit of the content of the hardwood pulp with respect to the entire pulp component in the pulp sheet for fluff pulp is not particularly limited, and can be, for example, 100% by mass.

[0129] The kappa value of the hardwood pulp used as the raw material pulp is preferably 0.3 or more, more preferably 0.35 or more, further preferably 0.4 or more, more further preferably 0.5 or more, still further preferably 0.75 or more, and particularly preferably 1.0 or more. In addition, the kappa value of the hardwood pulp is preferably 2.0 or less, more preferably 1.8 or less, further preferably 1.6 or less, and particularly preferably 1.5 or less. In the present embodiment, by causing the kappa value of the hardwood pulp to be within the above-described range, it is possible to more effectively reduce the liquid backflow rate of the fluff pad when the pulp sheet for fluff pulp is fluffed. In addition, by causing the kappa value of the hardwood pulp to be 0.3 or more, it is possible to not only reduce the bleaching chemicals at the time of pulp manufacturing, but also form straight fibers with less damage, and thus it is possible to improve the defibrillation of the pulp sheet for fluff pulp, and also reduce the amount of fine fibers.

[0130] The Canadian Standard Freeness (CSF) of the hardwood pulp measured in accordance with JIS P 8121-2:2012 is preferably 370 ml or more, more preferably 400 ml or more, and further preferably 430 ml or more. The Canadian Standard Freeness (CSF) of the hardwood pulp is a value measured for the hardwood pulp before papermaking.

[0131] The pulp sheet for fluff pulp according to the present embodiment can contain other raw material pulp in addition to the hardwood pulp. As the other raw material pulp, for example, there can be mentioned coniferous pulp, non-wood pulp, deinked pulp, and the like. As the hardwood pulp and the coniferous pulp, for example, there can be mentioned chemical pulp such as sulfite pulp (SP), alkaline pulp (AP), unbleached kraft pulp (UKP), and oxygen-bleached kraft pulp (OKP), semi-chemical pulp such as semi-chemical pulp (SCP) and chemical groundwood pulp (CGP), mechanical pulp such as groundwood pulp (GP) and thermomechanical pulp (TMP, BCTMP), and the like. In addition, there can be mentioned dissolving pulp (DP). As the non-wood pulp, for example, there can be mentioned cotton pulp such as linter and cotton linters, bamboo pulp, hemp, wheat straw, and bagasse. As the deinked pulp, for example, there can be mentioned deinked pulp obtained by using waste paper as a raw material. Among them, it is preferable to use a combination of hardwood bleached kraft pulp and coniferous bleached kraft pulp as the raw material pulp. By containing the hardwood bleached kraft pulp and the coniferous bleached kraft pulp in the pulp sheet for fluff pulp, it is possible to make the density of the fluff pad within an appropriate range when fluffing the pulp sheet for fluff pulp, and it is possible to more effectively reduce the backflow rate of liquid in the fluff pad.

[0132] The content of the coniferous pulp with respect to the total pulp component in the pulp sheet for fluff pulp is preferably 75% by mass or less, more preferably 70% by mass or less, further preferably 65% by mass or less, more further preferably 60% by mass or less, still further preferably 55% by mass or less, and particularly preferably 50% by mass or less. In addition, the lower limit of the content of the hardwood pulp with respect to the total pulp component in the pulp sheet for fluff pulp is not particularly limited, and for example, can be 0% by mass, and is preferably 5% by mass or more, and more preferably 10% by mass or more.

[0133] In the case where the pulp sheet for fluff pulp contains the coniferous pulp, the coniferous pulp is preferably coniferous bleached kraft pulp. The raw material of the coniferous bleached kraft pulp preferably contains at least one selected from the group consisting of Pinus, Pseudotsuga, and Cryptomeria, and more preferably contains at least one selected from the group consisting of Pinus and Pseudotsuga. In the present embodiment, it is preferable to use a combination of Pinus and Pseudotsuga.

[0134] The Canadian Standard Freeness (CSF) of the coniferous pulp measured in accordance with JIS P 8121-2:2012 is preferably 600 ml or more, more preferably 640 ml or more, and further preferably 670 ml or more. Among them, the Canadian Standard Freeness (CSF) of the coniferous pulp is a value measured for the coniferous pulp before papermaking.

[0135] The pulp board for fluff pulp can contain other pulp in addition to the broadleaf tree pulp and the coniferous tree pulp. As the other pulp, various kinds of pulp described above can be given. At this time, the content of the other pulp with respect to the entire pulp component in the pulp board for fluff pulp is preferably 10% by mass or less.

[0136] The length-weighted average fiber length of the broadleaf tree pulp used as the raw material pulp is preferably 0.50 mm or more, more preferably 0.60 mm or more, and further preferably 0.65 mm or more. In addition, the length-weighted average fiber length of the broadleaf tree pulp is preferably 1.20 mm or less, more preferably 1.10 mm or less, and further preferably 1.0 mm or less.

[0137] In addition, in the case where the coniferous tree pulp is also contained as the raw material pulp, the length-weighted average fiber length of the coniferous tree pulp is preferably 1.50 mm or more, more preferably 1.75 mm or more, and further preferably 2.00 mm or more. In addition, the length-weighted average fiber length of the coniferous tree pulp is preferably 3.50 mm or less, more preferably 3.20 mm or less, and further preferably 3.00 mm or less.

[0138] By making the fiber length of each of the pulps contained in the pulp board for fluff pulp be within the above range, it becomes easy to control the thickness and the density of the pulp board for fluff pulp within an appropriate range. In addition, by making the fiber length of each of the pulps contained in the pulp board for fluff pulp be within the above range, it is possible to more effectively reduce the backflow rate of the liquid in the fluff pad when fluffing the pulp board for fluff pulp. Note that the length-weighted average fiber length of each of the pulps contained in the pulp board for fluff pulp is measured in accordance with JIS P 8226-2:2011.

[0139] (Any Component)

[0140] The pulp board for fluff pulp can contain an additive as needed. As the additive, for example, a softening agent, a filler, a pigment, a sizing agent, a coagulant, an oil-resistant agent, aluminum sulfate, a retention agent, a drainage improver, a dry strength agent, a wet strength agent, a coloring pigment, a water-resistant agent, an antistatic agent, sodium sulfate, a surfactant, a pH adjusting agent (sodium hydroxide or the like), and the like can be given. The pulp board for fluff pulp of the present embodiment can also contain a softening agent. By making the pulp board for fluff pulp contain a softening agent, it is possible to more effectively improve the fibrillating property.

[0141] (Method for Manufacturing Pulp Board for Fluff Pulp)

[0142] The manufacturing method of the pulp sheet for fluff pulp according to the present embodiment preferably includes a cooking step of cooking wood chips containing broadleaf trees to become unbleached pulp, an oxygen delignification step, a bleaching step, and a sheeting step. In addition, a dewatering washing step, a classification step of fibers can be appropriately provided between the above steps, a pre-hydrolysis step can be provided before the cooking step, and a cold alkali step can be provided after the bleaching step. In addition, a beating step of beating the bleached pulp to a desired freeness can be provided before the sheeting step.

[0143] (cooking step)

[0144] In the cooking step, the broadleaf trees or the coniferous trees are cooked to obtain unbleached pulp. As the cooking method, a publicly known method can be employed. The cooking conditions in the cooking step are not particularly limited, and for example, in the case of using a sulfite cooking method, the sulfurization degree of the cooking liquor is preferably 15 to 45%, the cooking temperature is preferably 130 to 170°C, the effective alkali addition rate with respect to the unit mass of the dry wood is preferably 5 to 30% by mass, and the cooking time is preferably 45 to 500 minutes. The kappa number of the unbleached pulp obtained through the cooking step is preferably 10 to 70.

[0145] In the cooking step, it is preferable to perform the cooking by batchwise adding the cooking liquor. For example, in the first embodiment, by batchwise adding the cooking liquor, it is possible to control the alkali concentration in the entire cooking step, and as a result, it is possible to adjust the total content of the straight-chain fatty acid having 24 carbon atoms, the straight-chain fatty acid having 26 carbon atoms, and the straight-chain fatty acid having 28 carbon atoms in the obtained unbleached pulp. Specifically, by controlling the alkali concentration of the cooking liquor, it is possible to make the removal amount of the straight-chain fatty acid having 24 carbon atoms, the straight-chain fatty acid having 26 carbon atoms, and the straight-chain fatty acid having 28 carbon atoms be within an appropriate range.

[0146] In the second embodiment, by batchwise adding the cooking liquor, it is possible to control the alkali concentration in the entire cooking step, and as a result, it is possible to adjust the xylan content and the Canadian Standard Freeness (CSF) in the obtained unbleached pulp. Specifically, if the alkali concentration of the cooking liquor is increased, it is possible to reduce the xylan content and to reduce the Canadian Standard Freeness (CSF). On the contrary, if the alkali concentration of the cooking liquor is decreased, the xylan content becomes more, but it is possible to increase the Canadian Standard Freeness (CSF).

[0147] In the third embodiment, by adding the cooking liquor in batches, it is possible to control the alkali concentration in the entire cooking, and as a result, it is possible to adjust the amount of fine fibers in the unbleached pulp obtained. Specifically, if the alkali concentration of the cooking liquor is increased, the amount of fine fibers increases. On the contrary, if the alkali concentration of the cooking liquor is decreased, the amount of fine fibers decreases. Thus, in the case where wood chips that easily generate fine fibers are used as the pulp raw material, etc., a recipe that decreases the alkali concentration of the cooking liquor, or reduces the amount of fine fibers, etc., can be employed. Also, by controlling the cooking time and the cooking temperature, it is possible to adjust the amount of fine fibers in the unbleached pulp obtained. Specifically, if the cooking time is shortened or the cooking temperature is increased, the amount of fine fibers increases. On the contrary, if the cooking time is lengthened or the cooking temperature is decreased, the amount of fine fibers decreases. Thus, in the case where wood chips that easily generate fine fibers are used as the pulp raw material, etc., a method that lengthens the cooking time, or decreases the cooking temperature, etc., can be employed.

[0148] In the fourth embodiment, by adding the cooking liquor in batches, it is possible to control the alkali concentration in the entire cooking process, and as a result, it is possible to adjust the length-weighted average fiber length of the unbleached pulp obtained. Specifically, if the alkali concentration of the cooking liquor is increased, the length-weighted average fiber length becomes shorter. On the contrary, if the alkali concentration of the cooking liquor is decreased, the length-weighted average fiber length becomes longer. Thus, in the case where wood chips that have a short length-weighted average fiber length are used as the pulp raw material, etc., a recipe that decreases the alkali concentration of the cooking liquor, or makes the length-weighted average fiber length longer, etc., can be employed. Also, by controlling the cooking time and the cooking temperature, it is possible to adjust the length-weighted average fiber length of the unbleached pulp obtained. Specifically, if the cooking time is shortened or the cooking temperature is increased, the length-weighted average fiber length becomes shorter. On the contrary, if the cooking time is lengthened or the cooking temperature is decreased, the length-weighted average fiber length becomes longer. Thus, in the case where wood chips that have a short length-weighted average fiber length are used as the pulp raw material, etc., a method that lengthens the cooking time, or decreases the cooking temperature, etc., can be employed.

[0149] (Oxygen delignification process)

[0150] In the oxygen delignification process, an alkaline chemical and oxygen are added to the unbleached pulp, and the lignin is decomposed and dissolved into the alkaline chemical at high temperature and high pressure. By performing delignification in the oxygen delignification process, it is possible to reduce the amount of bleaching chemicals used in the subsequent multi-stage bleaching process, and it is possible to minimize the decrease in the pulp quality. As the oxygen delignification method, a well-known medium concentration method or a high concentration method can be directly applied, but a medium concentration method that is currently common, which is performed at a pulp concentration of 8 to 15 mass%, is preferable.

[0151] In the oxygen delignification process using the medium consistency method, as the alkali, caustic soda or oxidized kraft white liquor can be used, and as the oxygen, oxygen from cryogenic separation, oxygen from PSA (Pressure Swing Adsorption), or oxygen from VSA (Vacuum Swing Adsorption) or the like can be used. The oxygen and the alkali are added to the pulp slurry of the medium consistency in a medium consistency mixer, and after mixing is sufficiently performed, the mixture of the pulp, the oxygen, and the alkali is delivered under pressure to a reaction tower capable of retaining the mixture for a certain period of time, and delignification is performed. The addition rate of the oxygen is preferably 0.5 to 3 mass% with respect to the unit mass of the dry pulp, the addition rate of the alkali is preferably 0.5 to 4 mass%, the reaction temperature is preferably 80 to 120°C, the reaction time is preferably 15 to 100 minutes, and the pulp consistency is preferably 8 to 15 mass%. Other conditions can use known conditions. In the first embodiment, by appropriately controlling the alkali concentration in the oxygen delignification process, as a result, the total content of the straight-chain fatty acid having 24 carbon atoms, the straight-chain fatty acid having 26 carbon atoms, and the straight-chain fatty acid having 28 carbon atoms in the pulp can be adjusted. Specifically, if the alkali concentration is increased, the removal amount of the straight-chain fatty acid having 24 carbon atoms, the straight-chain fatty acid having 26 carbon atoms, and the straight-chain fatty acid having 28 carbon atoms becomes large. On the contrary, if the alkali concentration is decreased, the removal amount of the straight-chain fatty acid having 24 carbon atoms, the straight-chain fatty acid having 26 carbon atoms, and the straight-chain fatty acid having 28 carbon atoms becomes small. In addition, if caustic soda is used as the alkali, the removal amount of the straight-chain fatty acid having 24 carbon atoms, the straight-chain fatty acid having 26 carbon atoms, and the straight-chain fatty acid having 28 carbon atoms becomes large. On the contrary, if oxidized kraft white liquor is used as the alkali, the removal amount of the straight-chain fatty acid having 24 carbon atoms, the straight-chain fatty acid having 26 carbon atoms, and the straight-chain fatty acid having 28 carbon atoms becomes small.

[0152] In the second embodiment, by appropriately controlling the alkali concentration in the oxygen delignification process, as a result, the xylan content and the Canadian Standard Freeness (CSF) in the obtained pulp can be adjusted. Specifically, if the alkali concentration is increased, the xylan content becomes small, and the Canadian Standard Freeness (CSF) can be reduced. On the contrary, if the alkali concentration is decreased, the xylan content becomes large, but the Canadian Standard Freeness (CSF) can be increased. In addition, if caustic soda is used as the alkali, the xylan content becomes large, but the Canadian Standard Freeness (CSF) can be increased. On the contrary, if oxidized kraft white liquor is used as the alkali, the xylan content becomes small, but the Canadian Standard Freeness (CSF) becomes low.

[0153] In the third embodiment, by appropriately controlling the alkali concentration in the oxygen delignification step, as a result, the amount of fine fibers in the obtained pulp can be adjusted. Specifically, if the alkali concentration is increased, the fine fibers become more. In contrast, if the alkali concentration is decreased, the amount of fine fibers can be reduced. In addition, if caustic soda is used as the alkali, the amount of fine fibers can be reduced. In contrast, if oxidized sulfite white liquor is used as the alkali, the amount of fine fibers becomes more.

[0154] In the fourth embodiment, by appropriately controlling the alkali concentration in the oxygen delignification step, as a result, the length-weighted average fiber length of the obtained pulp can be adjusted. Specifically, if the alkali concentration is increased, the length-weighted average fiber length becomes shorter. In contrast, if the alkali concentration is decreased, the length-weighted average fiber length can be elongated. In addition, if caustic soda is used as the alkali, the length-weighted average fiber length can be elongated. In contrast, if oxidized sulfite white liquor is used as the alkali, the length-weighted average fiber length becomes shorter.

[0155] (Bleaching step)

[0156] In the bleaching step, the unbleached pulp subjected to the oxygen delignification is subjected to bleaching to obtain a bleached pulp. As the bleaching method, there is no particular limitation, and the bleaching can be performed using a publicly known bleaching method. As the bleaching method, for example, ozone bleaching stage (Z), chlorine dioxide bleaching stage (D), alkali extraction stage (E), oxygen bleaching stage (O), hydrogen peroxide bleaching stage (E / P), peracid bleaching stage (PA), acid washing stage (a), or acid treatment stage (A), and the like can be cited. In the present embodiment, for example, it is preferable to proceed in the order of D0-E / P-D1. Note that the Z stage causes large damage to the pulp fibers, and the rigidity of the fibers is lost, and thus the fibrillation of the pulp sheet deteriorates, and thus it is preferable not to be performed.

[0157] The bleaching conditions in the D0 stage and the D1 stage are not particularly limited, but the addition rate of chlorine dioxide is preferably 0.05 to 5.0 mass%, the bleaching temperature is preferably 30 to 90°C, the bleaching time is preferably 1 to 240 minutes, the pulp concentration is preferably 5 to 15 mass%, and the pH at the end of the reaction is preferably 2 to 6. In addition, the bleaching conditions in the E / P stage are not particularly limited, but the addition rate of hydrogen peroxide is preferably 0.05 to 5.0 mass%, the bleaching temperature is preferably 30 to 90°C, the bleaching time is preferably 1 to 240 minutes, the pulp concentration is preferably 5 to 15 mass%, and the pH at the end of the reaction is preferably 10 to 12.

[0158] (Pre-hydrolysis step)

[0159] A pre-hydrolysis step can be provided before the cooking step. In the pre-hydrolysis step, the hardwood or softwood is heated in the presence of water to perform a pre-hydrolysis treatment. Here, the amount of water relative to the hardwood or softwood (liquid ratio: amount (mass parts) of water / amount (mass parts) of hardwood or softwood) is preferably 1.0 to 10, more preferably 1.5 to 8.0, further preferably 2.0 to 7.0, and still further preferably 2.7 to 5.0. If the liquid ratio is 1.0 or more, hydrolysis sufficiently proceeds, and the reaction becomes uniform, so it is preferable. If the liquid ratio is 10 or less, the amount of heat required to heat to the desired temperature becomes small, so it is economical, and thus it is preferable. As the method of adding water, there is no particular limitation, and water can be added from the outside, or water originally contained in the hardwood or softwood can be used. In the case where steam is used at the time of heating, water contained in the steam can also be used. In addition, a medicine that directly or indirectly assists the hydrolysis of polysaccharides, such as an alkali, an acid, a chelating agent, and the like, can also be added together with water.

[0160] (cooling alkali step)

[0161] The pulp subjected to bleaching is further subjected to an alkali treatment, and a bleached pulp subjected to a cooling alkali treatment can be obtained. As the treatment method, there is no particular limitation, and as the alkali, caustic soda can be used. The addition rate of caustic soda is preferably 5.0 to 20.0%, the bleaching temperature is preferably 20 to 50°C, the bleaching time is preferably 1 to 240 minutes, and the pulp concentration is preferably 5 to 15% by mass.

[0162] (sheeting step)

[0163] In the sheeting step, first, the bleached pulp obtained through the bleaching step is dispersed in water to prepare a slurry. The concentration of the pulp contained in the slurry is preferably 0.01 to 10% by mass. In addition, in the case where an additive is added as needed, it is preferable to add the additive to the slurry.

[0164] In the sheeting step, a step of papermaking the slurry with a papermaking machine is included. The papermaking machine used in the papermaking step is not particularly limited, and for example, a long wire papermaking machine, a cylinder papermaking machine, a hybrid former, a gap former, or the like can be used. In addition, at the time of papermaking, the papermaking can be performed in such a manner that one layer is formed, or the papermaking can be performed in such a manner that a plurality of layers are laminated.

[0165] (dehydration and washing step)

[0166] A dewatering washing process can also be appropriately provided between the various processes described above. In the dewatering washing process, washing is performed by diluting the raw pulp and combining dewatering. The washing method is not particularly limited, and a publicly known washing machine can be used for washing. For example, a displacement washing method, a dilution-dewatering method, a pressurized washing method, or a washing method combining these methods can be used.

[0167] In the dewatering washing process, the amounts of the straight-chain fatty acid having 24 carbon atoms, the straight-chain fatty acid having 26 carbon atoms, and the straight-chain fatty acid having 28 carbon atoms removed at the time of washing can be changed by appropriately changing the ratio of filtered water / clean water used as washing water in the washing machine. Filtered water refers to water that is recycled as washing water, and clean water refers to ordinary water that is not recycled. In the first embodiment, specifically, by increasing the proportion of filtered water, the removal amounts of the straight-chain fatty acid having 24 carbon atoms, the straight-chain fatty acid having 26 carbon atoms, and the straight-chain fatty acid having 28 carbon atoms can be reduced, and by increasing the proportion of clean water, the removal amounts of the straight-chain fatty acid having 24 carbon atoms, the straight-chain fatty acid having 26 carbon atoms, and the straight-chain fatty acid having 28 carbon atoms can be increased. Thus, in the case where wood chips having a low content of the straight-chain fatty acid having 24 carbon atoms, the straight-chain fatty acid having 26 carbon atoms, and the straight-chain fatty acid having 28 carbon atoms are used as the pulp raw material, or the like, a method of increasing the proportion of filtered water in the washing water, a method of removing the straight-chain fatty acid having 24 carbon atoms, the straight-chain fatty acid having 26 carbon atoms, and the straight-chain fatty acid having 28 carbon atoms almost completely, or the like can be employed. In addition, by increasing the temperature of the washing water, the removal amounts of the straight-chain fatty acid having 24 carbon atoms, the straight-chain fatty acid having 26 carbon atoms, and the straight-chain fatty acid having 28 carbon atoms can be increased, and by decreasing the temperature of the washing water, the removal amounts of the straight-chain fatty acid having 24 carbon atoms, the straight-chain fatty acid having 26 carbon atoms, and the straight-chain fatty acid having 28 carbon atoms can be reduced.

[0168] In the third embodiment, in the dewatering washing process, the amount of fine fibers removed at the time of washing can be changed by appropriately changing the ratio of filtered water / clean water used as washing water in the washing machine. Filtered water refers to water that is recycled as washing water, and clean water refers to ordinary water that is not recycled. Specifically, by increasing the proportion of filtered water, the removal amount of fine fibers can be reduced, and by increasing the proportion of clean water, the removal amount of fine fibers can be increased. Thus, in the case where wood chips that easily generate fine fibers are used as the pulp raw material, or the like, a method of reducing the proportion of filtered water in the washing water, a method of removing fine fibers, or the like can be employed.

[0169] Further, in the fourth embodiment, in the dewatering and cleaning step, the length-weighted average fiber length can be adjusted by appropriately changing the ratio of filtered water / clean water used as the cleaning water in the cleaning machine. The filtered water refers to water that is recycled as the cleaning water, and the clean water refers to ordinary water that is not recycled. Specifically, by increasing the proportion of filtered water, the amount of fine fibers removed can be reduced, and the length-weighted average fiber length can be made shorter, but by increasing the proportion of clean water, the amount of fine fibers removed can be increased, and the length-weighted average fiber length can be made longer. Thus, in the case where wood chips having a short length-weighted average fiber length are used as the pulp raw material, and the like, a method of reducing the proportion of filtered water in the cleaning water, removing fine fibers, and the like can be employed.

[0170] (Fiber classifying step)

[0171] A fiber classifying step can also be appropriately provided between the various steps described above. In the fine fiber removal step, the raw material pulp is diluted and passed through a screen, thereby classifying the fibers. In particular, in the third embodiment, it is preferable to classify the fibers using a metal mesh or a metal screen before the sheeting step. By providing such a classifying step, fine fibers pass through the mesh or screen, and thus fine fibers can be removed. Further, fine fibers that have passed through the mesh can also be recovered in advance using the method described above, and added to a substance in which the amount of fine fibers is desired to be increased, thereby increasing the amount of fine fibers. For example, in a laboratory, pulp can be washed with water on a stainless steel screen, or fine fibers can be removed and recovered using a screen separation device (for example, a screen separation tester according to JIS P 8207:2009, TAPPI T233 cm-95 (for example, a Paller-Mcute fiber screen separation tester)). In actual production, a fiber classifying machine can be used, thereby enabling removal and recovery of fine fibers.

[0172] (Fluff pad)

[0173] The present embodiment relates to a fluff pad formed from the fluff pulp sheeting described above. The fluff pad in the present specification refers to one in which fluff pulp obtained by defibrating the fluff pulp sheeting described above is formed into a sheet shape. The fluff pad of the present embodiment has excellent water absorbency and can hold liquid after absorbing the liquid. Thus, in the fluff pad of the present embodiment, the backflow rate of liquid is reduced.

[0174] The conditions for defibrating the fluff pulp sheeting are not particularly limited, and a publicly known defibrator, a pulverizer, or the like can be used.

[0175] The fluff pad is formed by stacking fluff pulp under an air stream. Specifically, it is formed by transporting defibrated fluff pulp using air, and stacking it on a metal mesh or a porous base material such as tissue paper or nonwoven fabric.

[0176] The density of the fluff mat is preferably 0.058 g / cm 3 More preferably, the density is 0.060 g / cm 3 More preferably, the density is 0.060 g / cm 3 More preferably, the density is 0.060 g / cm 3 By setting the density of the fluff mat within the above range, the thickness of the fluff mat can be made thin.

[0177] (Absorbent article)

[0178] The present embodiment can also relate to an absorbent article having the above fluff mat. As the absorbent article, for example, a paper diaper, an absorbent pad, a light incontinence pad, a sanitary napkin for menstruation, and the like can be given. The fluff mat of the present embodiment is particularly capable of neutralizing acidic urine.

[0179] Example

[0180] The following examples and comparative examples will more specifically describe the features of the present application. The materials, amounts, ratios, processing contents, processing steps, and the like shown in the following examples can be appropriately changed as long as the gist of the present application is not deviated. Therefore, the scope of protection of the present application should not be interpreted limitatively by the specific examples shown below.

[0181] [Preparation of coniferous pulp]

[0182] [Digestion]

[0183] After mixing wood chips of Pinus and Pseudotsuga at 30:70 in terms of absolute dry mass, 200 g was collected in terms of absolute dry mass and put in a 2.5 liter capacity autoclave, and digestion was performed under conditions of a liquor ratio of 5, a sulfidity of 28% of the cooking liquor, an alkali addition rate of 22%, a cooking temperature of 165°C, and a cooking time of 120 minutes. After that, the black liquor was separated from the pulp, and the pulp was refined using a flat screen having a screen with 10 screen slots to obtain unbleached pulp having a kappa number of about 30.

[0184] [Oxygen delignification]

[0185] After 70.0 g of unbleached pulp in terms of absolute dry mass was collected, sodium hydroxide was added at 2.0% by mass with respect to the mass of the absolute dry pulp, and then diluted with ion exchange water to adjust the pulp concentration to 10% by mass. This was put in a heated autoclave, 99.9% of commercially available compressed oxygen was injected, and oxygen delignification was performed at 95°C for 60 minutes at a gauge pressure of 0.5 MPa. The obtained pulp was diluted with ion exchange water to 3% by mass, and then dewatered and washed using a Buchner funnel.

[0186] [Blanching]

[0187] A 60 g of kraft pulp after oxygen alkaline delignification was collected in terms of absolute dry mass, put into a plastic bag, and ion exchange water was used to adjust the pulp concentration to 10 mass%, and chlorine dioxide was added at 2.0 mass% relative to the absolute dry pulp mass. This was immersed in a constant temperature water tank at 70°C for 60 minutes to perform D0-stage treatment. The obtained pulp was diluted to 3 mass% with ion exchange water, and dewatering and washing were performed using a Buchner funnel.

[0188] The pulp after the D0-stage was put into a plastic bag, ion exchange water was added, the pulp concentration was adjusted to 10 mass%, and caustic soda was added at 1.0 mass% relative to the absolute dry pulp mass, and hydrogen peroxide was added at 0.2 mass% relative to the absolute dry pulp mass, and mixed well. Thereafter, it was immersed in a constant temperature water tank at 70°C for 90 minutes to perform E / P-stage treatment. The obtained pulp was diluted to 3 mass% with ion exchange water, and dewatering and washing were performed using a Buchner funnel.

[0189] The pulp after the E / P-stage was put into a plastic bag, ion exchange water was used to adjust the pulp concentration to 10 mass%, and caustic soda was added at 1.0 mass% relative to the absolute dry pulp mass, and hydrogen peroxide was added at 0.3 mass% relative to the absolute dry pulp mass, and mixed well. Thereafter, it was immersed in a constant temperature water tank at 70°C for 90 minutes to perform P-stage treatment. The obtained pulp was diluted to 3 mass% with ion exchange water, and dewatering and washing were performed using a Buchner funnel.

[0190] The pulp after the P-stage was put into a plastic bag, ion exchange water was used to adjust the pulp concentration to 10 mass%, and chlorine dioxide was added at 0.2 mass% relative to the absolute dry pulp mass, and immersed in a constant temperature water tank at 70°C for 60 minutes to perform D1-stage bleaching. The obtained bleached coniferous pulp was diluted to 3 mass% with ion exchange water, and dewatering and washing were performed using a Buchner funnel.

[0191] [Preparation of broadleaf tree pulp]

[0192] [Digestion]

[0193] Wood chips of Eucalyptus and Acacia (Acacia mangium) were mixed at 30:70 in terms of absolute dry mass ratio, and 200 g was collected in terms of absolute dry mass, put into a 2.5 liter capacity autoclave, and kraft digestion was performed under conditions of liquid ratio 5, sulfidity of cooking liquor 28%, alkali addition rate 20%, cooking temperature 155°C, and cooking time 120 minutes. Thereafter, the black liquor was separated from the pulp, and the pulp was refined using a flat screen having a screen plate with 8 screen slots to obtain unbleached pulp having a kappa number of about 18.

[0194] [Oxygen delignification]

[0195] A 70.0 g of unbleached pulp was collected in terms of absolute dry mass, caustic soda was added at 2.0 mass% relative to the mass of the absolute dry pulp, and then diluted with ion exchange water to adjust the pulp concentration to 10 mass%. This was put into a heated autoclave, 99.9% of commercially available compressed oxygen was injected to make the gauge pressure 0.5 MPa, and oxygen delignification was performed at 95°C for 60 minutes. The obtained pulp was diluted with ion exchange water to 3 mass%, and then dewatered and washed with a Buchner funnel.

[0196] [bleaching]

[0197] A 60 g of kraft pulp after oxygen-alkali delignification was collected in terms of absolute dry mass, put into a plastic bag, and ion exchange water was used to adjust the pulp concentration to 10 mass%, and then chlorine dioxide was added at 1.0 mass% relative to the mass of the absolute dry pulp. This was immersed in a constant-temperature water tank at 70°C for 60 minutes to perform D0-stage treatment. The obtained pulp was diluted with ion exchange water to 3 mass%, and then dewatered and washed with a Buchner funnel.

[0198] The pulp after the D0-stage was put into a plastic bag, ion exchange water was added to adjust the pulp concentration to 10 mass%, and then caustic soda was added at 1.0 mass% relative to the mass of the absolute dry pulp, and hydrogen peroxide was added at 0.2 mass% relative to the mass of the absolute dry pulp, and mixed well. After that, it was immersed in a constant-temperature water tank at 70°C for 90 minutes to perform E / P-stage treatment. The obtained pulp was diluted with ion exchange water to 3 mass%, and then dewatered and washed with a Buchner funnel.

[0199] The pulp after the E / P-stage was put into a plastic bag, ion exchange water was used to adjust the pulp concentration to 10 mass%, and then chlorine dioxide was added at 0.2 mass% relative to the mass of the absolute dry pulp, and immersed in a constant-temperature water tank at 70°C for 60 minutes to perform D1-stage bleaching. The obtained bleached hardwood pulp was diluted with ion exchange water to 3 mass%, and then dewatered and washed with a Buchner funnel.

[0200] (Example 1)

[0201] The bleached softwood pulp and bleached hardwood pulp after the D1-stage were mixed at a ratio of 0:100 in terms of absolute dry mass, and then diluted with ion exchange water to a concentration of about 0.5 mass%, and then a circular standard hand paper machine (manufactured by Kumagai Riki Kogyo Co., Ltd.) was used to perform papermaking to make the basis weight 270 g / m 2 , and a fluff pulp sheet was obtained.

[0202] (Example 2)

[0203] In Example 1, the absolute dry mass ratio of the bleached coniferous pulp to the bleached broad-leaved pulp at the time of sheet formation was set to 20:80, and the same operation was performed except for this to obtain a pulp sheet for fluff pulp.

[0204] (Example 3)

[0205] In Example 1, the absolute dry mass ratio of the bleached coniferous pulp to the bleached broad-leaved pulp at the time of sheet formation was set to 40:60, and the same operation was performed except for this to obtain a pulp sheet for fluff pulp.

[0206] (Example 4)

[0207] In Example 1, the absolute dry mass ratio of the bleached coniferous pulp to the bleached broad-leaved pulp at the time of sheet formation was set to 60:40, and the same operation was performed except for this to obtain a pulp sheet for fluff pulp.

[0208] (Example 5)

[0209] In Example 1, the alkali addition rate was set to 18% in a manner that the kappa value of the unbleached pulp used in the preparation of the bleached broad-leaved pulp became 25, the chlorine dioxide addition rate of the D0 stage was changed to 2.0 mass%, and the absolute dry mass ratio of the bleached coniferous pulp to the bleached broad-leaved pulp at the time of sheet formation was set to 20:80, and the same operation was performed except for this to obtain a pulp sheet for fluff pulp.

[0210] (Example 6)

[0211] In Example 1, the alkali addition rate was set to 22% in a manner that the kappa value of the unbleached pulp used in the preparation of the bleached broad-leaved pulp became 13, the chlorine dioxide addition rate of the D0 stage was set to 0.7 mass%, and the absolute dry mass ratio of the bleached coniferous pulp to the bleached broad-leaved pulp at the time of sheet formation was set to 20:80, and the same operation was performed except for this to obtain a pulp sheet for fluff pulp.

[0212] (Example 7)

[0213] In Example 1, the chlorine dioxide addition rate of the D0 stage at the time of preparation of the bleached broad-leaved pulp was set to 0.8 mass%, the chlorine dioxide addition rate of the D0 stage at the time of preparation of the bleached coniferous pulp was set to 1.3 mass%, and the absolute dry mass ratio of the bleached coniferous pulp to the bleached broad-leaved pulp at the time of sheet formation was set to 20:80, and the same operation was performed except for this to obtain a pulp sheet for fluff pulp.

[0214] (Example 8)

[0215] In Example 1, the addition rate of chlorine dioxide at the D0 stage in the preparation of the bleached hardwood pulp was set to 1.7 mass%, the addition rate of chlorine dioxide at the D0 stage in the preparation of the bleached softwood pulp was set to 2.2 mass%, the dry mass ratio of the bleached softwood pulp to the bleached hardwood pulp was set to 20:80, and the same operation as in Example 1 was performed except for the above, to obtain a pulp sheet for fluff pulp.

[0216] (Example 9)

[0217] In Example 1, the dry mass ratio of the bleached softwood pulp to the bleached hardwood pulp at the time of sheet formation was set to 20:80, and after dilution to a concentration of about 0.5 mass%, a softening agent (FS-8010, manufactured by Seiko PMC Corporation, active ingredient 90 mass%) was added so that the active ingredient would be 0.1 mass% with respect to the dry mass of the pulp, and the same operation as in Example 1 was performed except for the above, to obtain a pulp sheet for fluff pulp.

[0218] (Example 10)

[0219] In Example 9, the amount of the softening agent was changed so that the active ingredient would be 0.3 mass% with respect to the dry mass of the pulp, and the same operation as in Example 9 was performed except for the above, to obtain a pulp sheet for fluff pulp.

[0220] (Comparative Example 1)

[0221] In Example 1, the dry mass ratio of the bleached softwood pulp to the bleached hardwood pulp at the time of sheet formation was set to 80:20, and the same operation as in Example 1 was performed except for the above, to obtain a pulp sheet for fluff pulp.

[0222] (Comparative Example 2)

[0223] In Example 1, after the oxygen delignification in the preparation of the bleached hardwood pulp, the pulp was washed with 10 L of hot water (90°C), the dilution of the D0 stage, the E / P stage, and the D1 stage after the treatment with ion exchange water was set to 5 mass%, the dry mass ratio of the bleached softwood pulp to the bleached hardwood pulp at the time of sheet formation was set to 20:80, and the same operation as in Example 1 was performed except for the above, to obtain a pulp sheet for fluff pulp.

[0224] (Comparative Example 3)

[0225] In Example 1, the Acacia genus of the hardwood tree was changed to Acacia crassicarpa, the dry mass ratio of the bleached softwood pulp to the bleached hardwood pulp at the time of sheet formation was set to 20:80, and the same operation as in Example 1 was performed except for the above, to obtain a pulp sheet for fluff pulp.

[0226] (Comparative Example 4)

[0227] In Example 1, the same operation was performed except that the absolute dry mass ratio of bleached coniferous pulp to bleached broad-leaved pulp at the time of sheeting was set to 100:0, and a pulp sheet for fluff pulp was obtained.

[0228] (Measurement evaluation)

[0229] [ISO whiteness]

[0230] Measured in accordance with JIS P 8148:2018.

[0231] [Viscosity]

[0232] Measured in accordance with JIS P 8215:1998.

[0233] [Kappa number]

[0234] Measured in accordance with JIS P 8211:2011.

[0235] [Linear fatty acids of C24, C26, C28]

[0236] The pulp sheet for fluff pulp was dried, and about 200 mg of the dried pulp was accurately weighed, 0.1 ml of concentrated hydrochloric acid (12 equivalents) and 2 ml of chloroform were added, and ultrasonic treatment was performed for 10 minutes. The obtained extract was filtered with a membrane filter (pore size 0.2 μm). The above filtrate was analyzed by high-performance liquid chromatography. As an eluent, methanol: acetone containing 0.1 mass% of trifluoroacetic acid = 50:50 was used. In addition, the flow rate of the high-performance liquid chromatography was set to 1 ml / minute. The column used was X Bridge C18 manufactured by Waters, 250 mm x 4.6 mm I.D, the temperature was 30°C, and 2 μl of the filtrate was injected. The detector used was a charged particle detector, and linear fatty acids (higher fatty acids C 23 H 47 COOH, C 25 H 51 COOH, C 27 H 55 COOH) were detected. The concentration in the sample was calculated for each by the following calculation formula, and the total concentration was calculated. The peak area value of each component was calculated as follows: for peaks that are portions surrounded by a baseline and each peak but are partially repeated, the peak separation was performed by the perpendicular line method of JIS K0124:2011.

[0237] [Calculation formula]

[0238] Concentration in sample (ppm) = standard sample concentration (100 ppm) / standard sample peak area value x sample peak area value x 2 (ml) / (sample mass (mg) / 1000)

[0239] [Appearance (dirt)]

[0240] The number of inclusions in the pulp board used for making the fluff pulp was visually measured. Regarding inclusions, the size recorded in the inclusion measurement chart of JIS P 8208:1998 was determined to be 0.05 mm. 2 The above-mentioned inclusions. The inclusions were measured on a total of 5 pulp boards for fluff pulp, and the number of inclusions per 100g of oven-dry pulp was taken as the number of inclusions.

[0241] [Fibrinolytic]

[0242] The defiberability evaluation of fluff pulp sheets was conducted at 23°C and 50% relative humidity. Fluff pulp sheets, after humidity adjustment at 23°C and 50% relative humidity, were cut into 10mm x 10mm squares, and 3g of each sheet was measured and added to a Wonder Blender (manufactured by OSAKA CHEMICAL Co., Ltd., model WB-1, speed 25000rpm) without deviation. Defibering was performed at 5-second intervals for a specified time to make the pulp fluffy (hereinafter, the fluffy pulp that becomes fluffy through defibering will be referred to as "fluff pulp"). Next, the fluff pulp was immersed in water, gently stirred with a stick, and then a standard circular hand-operated paper machine was used to produce a basis weight of 25g / m³. 2 The defiberability of handmade paper was evaluated by visual observation. The time (in seconds) required for the unfiber to disappear was used as the indicator for evaluating defiberability.

[0243] [Making a Plush Mat]

[0244] Use at 23℃ and 50% relative humidity. Figure 1 The shown plush mat making apparatus 100 performs the making of plush mats. Here, the plush mat making apparatus 100 uses a pulp desiccant 5 (manufactured by Maruta Manufacturing Co., Ltd.), a stainless steel sieve 22 with a mesh size of 180μm (manufactured by AS ONE Co., Ltd., inner diameter 75mm × inner height 20mm), a stainless steel sieve 24 with a mesh size of 150μm (manufactured by AS ONE Co., Ltd., inner diameter 75mm × inner height 20mm), a column 20 made from a PET resin board cut into 70cm × 40cm pieces (manufactured by ACRYSUNDAY CO.,LTD., Sunday PET, thickness 0.5mm), a polypropylene powder funnel 10 (manufactured by AS ONE Co., Ltd., model No. 166, mouth diameter 180mm, foot outer diameter 43mm, foot length 48mm), a polypropylene powder funnel 30 (manufactured by AS ONE Co., Ltd., model No. 169, mouth diameter 120mm, foot outer diameter 30mm, foot length 27mm), and a household vacuum cleaner 40 (Hitachi Home & Life). Solution Corporation manufactured, model CV-CF4), assembled into Figure 1The device thus configured. First, the total weight of the stainless steel screen of 180 μm mesh and the column was measured in advance. Next, the pulp defiberer and the household vacuum cleaner were started. The suction power of the household vacuum cleaner was set to weak (suction power of about 80 W), and the fluff pulp obtained in the evaluation of the defiberability without un-defibered material was fed little by little from the upper portion of the fluff pad making device. The weight of the fluff pad formed on the stainless steel screen of 180 μm mesh was measured occasionally, and the formation of the fluff pad was continued until 200 g / m 2 was reached. 2 After 200 g / m 2 was reached, the pulp defiberer and the household vacuum cleaner were stopped. After the column was removed, the surface of the fluff pad was gently pressed with a circular stainless steel plate to adjust the shape, and the fluff pad (diameter 75 mm) was gently taken out from the screen of 180 μm mesh without damaging the shape. In addition, the face in contact with the stainless steel screen was defined as the wire face of the fluff pad.

[0245] [Measurement of the backflow rate of the fluff pad]

[0246] The measurement of the backflow rate of the fluff pad was performed in an environment of 23°C and a relative humidity of 50%. The fluff pad of 200 g / m 2 made was placed on a 5-mm-thick acrylic plate with the wire face as the upper surface. After a 2-mm-thick spacer was sandwiched, another 5-mm-thick acrylic plate was placed from above, and a table press was pressed for 10 minutes. After the pressing was completed, the placed acrylic plate was removed from above, and the sample was left to stand for 30 minutes. A stainless steel base plate (5 mm thick, 11 x 11 cm) was placed on a horizontal test bench, and two pieces of the fluff pad (total basis weight of the fluff pad 400 g / m 2 ) were overlaid thereon with the wire face as the upper surface. A 11-cm x 11-cm square core wrap tissue (manufactured by Oji Nepia Co., Ltd., basis weight 16 g / m 2), so that the flow direction of the paper becomes the longitudinal direction. After 10 seconds, 20 g of artificial urine was injected into the hole of the strike through plate (10 cm x 10 cm, thickness 85 mm, weight 665 g) made of stainless steel and having a hole of 25 mm in diameter in the central portion. After the artificial urine was completely absorbed, the strike through plate was removed immediately. Next, a 11 cm x 11 cm square polyethylene sheet was placed on the core wrap paper, a 11 cm x 11 cm square sponge rubber sheet (AS ONE Corporation, thickness 10 mm, hardness (ASKER C hardness tester): 45 degrees) was placed thereon, a 11 cm x 11 cm square acrylic plate of 5 mm in thickness was placed thereon, and a 2.2 kg weight was placed thereon. The total weight of the polyethylene sheet, the sponge rubber sheet, the two acrylic plates, and the 2.2 kg weight was 2.31 kg, and the area of the fluff pad was 0.00442 m 2 Therefore, the pressure applied to the fluff pad was 5.1 kPa. The pressure was applied for 3 minutes at 5.1 kPa. Next, the polyethylene sheet, the sponge rubber sheet, the two acrylic plates, and the 2.2 kg weight were removed, and 10 pieces of 11 cm x 11 cm square filter paper (ADVANTEC Corporation, No. 1640) that had been conditioned in an environment of 23°C and 50% relative humidity and whose weights were known were placed so that the surfaces contacted the core wrap paper of the diaper, and the transparent folder, the polyurethane rubber sheet, the two acrylic plates, and the 2.2 kg weight were placed again, and the pressure was applied for 2 minutes while the filter paper absorbed the artificial urine. After 2 minutes, the 10 pieces of filter paper were taken out, and the weights were measured, and the backflow rate was measured using the following calculation formula. The artificial urine used here was prepared according to the following procedure. First, methylene blue (Showa Chemical Industry Co., Ltd.) was dissolved in ion exchange water to prepare a 0.50 mass% methylene blue aqueous solution. Next, in a 500 ml beaker, 19.40 g of urea (Showa Chemical Industry Co., Ltd.), 8.040 g of sodium chloride (Showa Chemical Industry Co., Ltd.), 2.045 g of magnesium sulfate 7 hydrate (Showa Chemical Industry Co., Ltd.), and 0.835 g of calcium chloride 2 hydrate were measured sequentially, an appropriate amount of ion exchange water was added, and 1.50 g of the 0.50 mass% methylene blue aqueous solution was added dropwise. Next, the solution was transferred to a 1 L capacity volumetric flask, and the volume was made 1 L to prepare the artificial urine.

[0247]

[0248] [Table 1]

[0249]

[0250] In the examples, a fluff pulp sheet having a good appearance was obtained, and a fluff pad in which the backflow rate was suppressed was obtained. In addition, the fluff pulp sheet obtained in the examples had good fibrillation.

[0251] (Example 21)

[0252] The bleached coniferous pulp after Dl section was mixed with the bleached broadleaf pulp at a ratio of 0: 100 in terms of absolute dry mass, and diluted with ion exchange water to a concentration of about 0.5 mass%, and then pulp sheeting was performed using a circular standard hand sheet machine (Kumagai Rikagaku Kogyo Co., Ltd.) so that the basis weight became 270 g / m2, to obtain fluff pulp sheeting. 2

[0253] (Example 22)

[0254] In Example 21, the absolute dry mass ratio of the bleached coniferous pulp to the bleached broadleaf pulp at the time of sheeting was set to 40: 60, and the same operation was performed except for this, to obtain fluff pulp sheeting.

[0255] (Example 23)

[0256] In Example 21, the absolute dry mass ratio of the bleached coniferous pulp to the bleached broadleaf pulp at the time of sheeting was set to 60: 40, and the same operation was performed except for this, to obtain fluff pulp sheeting.

[0257] (Example 24)

[0258] In Example 21, the absolute dry mass ratio of the eucalyptus genus and the acacia genus (Acacia mangium) of the broadleaf tree was set to 0: 100, and the absolute dry mass ratio of the bleached coniferous pulp to the bleached broadleaf pulp at the time of sheeting was set to 0: 100, and the same operation was performed except for this.

[0259] (Example 25)

[0260] In Example 21, the absolute dry mass ratio of the eucalyptus genus and the acacia genus (Acacia mangium) of the broadleaf tree was set to 100: 0, and the absolute dry mass ratio of the bleached coniferous pulp to the bleached broadleaf pulp at the time of sheeting was set to 0: 100, and the same operation was performed except for this.

[0261] (Example 26)

[0262] ​In Example 21, the absolute dry mass ratio of eucalyptus of broadleaf trees to acacia (Acacia mangium) was set to 100:0, the bleached broadleaf tree pulp after D1 was put in a plastic bag, sodium hydroxide was added in a manner that the mass ratio relative to the absolute dry mass of the pulp was 7.5 mass%, after the pulp concentration was adjusted to 10 mass% using ion exchange water, cold alkali treatment was performed by immersing in a constant temperature water tank at 40°C for 60 minutes. The obtained bleached broadleaf tree pulp after cold alkali treatment was diluted to 3 mass% using ion exchange water, and then dehydrated and washed using a Buchner funnel. The bleached broadleaf tree pulp after cold alkali treatment was diluted to a concentration of about 0.5 mass%, and then pulp sheets for fluff pulp were obtained by performing papermaking using a circular standard hand paper machine (manufactured by Kumagai Riki Kogyo Co., Ltd.) in a manner that the basis weight became 270 g / m2. 2 The same operation as in Example 21 was performed except for the above operation.

[0263] (Example 27)

[0264] In Example 21, after dilution to a concentration of about 0.5 mass% at the time of papermaking, a softening agent (FS-8010, manufactured by Seiko PMC Co., Ltd., active ingredient 90%) was added so that the active ingredient became 0.1 mass% relative to the absolute dry mass of the pulp, and the same operation was performed except for this.

[0265] (Example 28)

[0266] In Example 21, after dilution to a concentration of about 0.5 mass% at the time of papermaking, a softening agent was added so that the active ingredient became 0.3 mass% relative to the absolute dry mass of the pulp, and the same operation was performed except for this.

[0267] (Comparative Example 21)

[0268] In Example 21, the absolute dry mass ratio of bleached needle leaf tree pulp to bleached broadleaf tree pulp at the time of papermaking was set to 100:0, and the same operation was performed except for this, to obtain pulp sheets for fluff pulp.

[0269] (Comparative Example 22)

[0270] In Example 21, the pulp concentration was dehydrated to 10 mass% at the time of papermaking, and then diluted to a concentration of about 0.5 mass% after beating with a PFI mill (manufactured by Kumagai Riki Kogyo Co., Ltd.) for 10,000 revolutions, and the same operation was performed except for this.

[0271] (Comparative Example 23)

[0272] In Example 21, the acacia of the broadleaf trees was Acacia mearnsii, and the same operation was performed except for this.

[0273] (Measurement and Evaluation)

[0274] [Amount of xylan]

[0275] The amount of xylan (%) was calculated from the obtained data, based on the following formula.

[0276] Amount of xylan (g) = Amount of xylose measurement (μM) x 132 (molecular weight of xylose unit) / Over-degradation rate of acid-based sugars (%)

[0277] Amount of xylan (%) = Amount of xylan (g) / Mass of pulp board for fluff pulp supplied to ion chromatography

[0278] [K value]

[0279] Determined in accordance with JIS P 8206:1982.

[0280] [Canadian Standard Freeness]

[0281] The pulp board for fluff pulp was disintegrated to obtain disintegrated pulp in accordance with JIS P 8220-1:2012. The Canadian Standard Freeness (CSF) of the disintegrated pulp was determined in accordance with JIS P 8121-2:2012.

[0282] [ISO whiteness]

[0283] Determined in accordance with JIS P 8148:2018.

[0284] [Kappa value]

[0285] Determined in accordance with JIS P 8211:2011.

[0286] [Amount of change in whiteness]

[0287] The pulp board for fluff pulp was subjected to heat treatment at 105°C in accordance with JIS P 8154-1:2008. The heat treatment time was set to 72 hours. After the heat treatment, the ISO whiteness of the pulp board for fluff pulp was determined in accordance with JIS P 8148:2018. The amount of change in ISO whiteness was calculated by the following formula.

[0288] Amount of change in ISO whiteness (%) = B0 (%) - B1 (%)

[0289] Here, B0 represents the ISO whiteness of the pulp board for fluff pulp before the heat treatment, and B1 represents the ISO whiteness of the pulp board for fluff pulp after the heat treatment.

[0290] [Fibrillation]

[0291] Evaluation of the fibrillation of the pulp sheet for fluff pulp was performed in an environment of 23°C and 50% relative humidity. The pulp sheet for fluff pulp, which had been humidity-adjusted in an environment of 23°C and 50% relative humidity, was cut into 10 mm x 10 mm squares, 3 g was weighed, and was put into a Wonder blender (OSAKA CHEMICAL Co., Ltd., Model WB-1, rotation speed 25000 rpm) in a non-biased manner. Fibrillation was performed for a prescribed time at intervals of 5 seconds, and the pulp was made into a cotton-like state (hereinafter, the pulp made into a cotton-like state by fibrillation will be referred to as "fluff pulp"). Next, the fluff pulp was immersed in water, and after being gently stirred with a rod, a hand sheet for fibrillation evaluation having a basis weight of 25 g / m 2 was produced using a circular standard hand paper machine. The hand sheet for fibrillation evaluation was visually observed, and the fibrillation time (seconds) required until the non-fibrillated material disappeared was taken as an index of the fibrillation evaluation.

[0292] [Production of fluff pad]

[0293] A fluff pad was produced in the same manner as in the above [Production of fluff pad].

[0294] [Measurement of backflow rate of fluff pad]

[0295] The backflow rate of the fluff pad was measured in the same manner as in the above [Measurement of backflow rate of fluff pad].

[0296] [Table 2]

[0297]

[0298] In the examples, a pulp sheet for fluff pulp having high whiteness and excellent fibrillation was obtained, as compared with the comparative examples. In addition, in the examples, a fluff pad in which the backflow rate was suppressed was obtained.

[0299] (Example 31)

[0300] The bleached coniferous pulp after the D1 section was mixed with the bleached broadleaf pulp at a ratio of 20:80 in terms of absolute dry mass, and after being diluted with ion exchange water to a concentration of about 0.5 mass%, pulp was produced using a circular standard hand paper machine (Kumagai Riki Kogyo Co., Ltd.) in such a manner that the basis weight became 270 g / m 2 to obtain a pulp sheet for fluff pulp.

[0301] (Example 32)

[0302] In Example 31, the absolute dry mass ratio of the bleached coniferous pulp to the bleached broadleaf pulp at the time of pulp production was set to 60:40, and the same operation was performed except for this to obtain a pulp sheet for fluff pulp.

[0303] (Example 33)

[0304] In Example 31, the kappa value of unbleached kraft pulp at the time of preparing the bleached broadleaf pulp was set to 13, the chlorine dioxide addition rate in D0 section was set to 0.7 mass%, and the same operation was performed except for this, to obtain a pulp sheet for fluff pulp.

[0305] (Example 34)

[0306] In Example 31, the absolute dry mass ratio of bleached coniferous pulp to bleached broadleaf pulp at the time of sheet formation was set to 0:100, and the same operation was performed except for this, to obtain a pulp sheet for fluff pulp.

[0307] (Example 35)

[0308] In Example 34, 20 g of the bleached broadleaf pulp after D1 section was placed on a 80-mesh stainless steel sieve, and the fine fibers were removed while stirring with hands with spraying of ion exchange water. At this time, the amount of ion exchange water was set to 20 L. The same operation was repeated until the pulp required for sheet formation could be ensured. The pulp remaining on the stainless steel sieve after the operation was supplied to sheet formation, and the same operation as Example 34 was performed except for this.

[0309] (Example 36)

[0310] In Example 34, 20 g of the bleached broadleaf pulp after D1 section was placed on a 60-mesh stainless steel sieve, and the fine fibers were removed while stirring with hands with spraying of ion exchange water. At this time, the amount of ion exchange water was set to 100 L. The same operation was repeated until the pulp required for sheet formation could be ensured. The pulp remaining on the stainless steel sieve after the operation was supplied to sheet formation, and the same operation as Example 34 was performed except for this.

[0311] (Example 37)

[0312] In Example 31, the absolute dry mass ratio of bleached coniferous pulp to bleached broadleaf pulp at the time of sheet formation was set to 20:80, and after dilution to a concentration of about 0.5 mass%, a softener (FS-8010, manufactured by Seiko PMC Corporation, active ingredient 90 mass%) was added so that the active ingredient became 0.1 mass% with respect to the absolute dry mass of the pulp, and the same operation was performed except for this, to obtain a pulp sheet for fluff pulp.

[0313] (Example 38)

[0314] In Example 31, the absolute dry mass ratio of bleached coniferous pulp to bleached broad-leaved pulp at the time of sheet formation was set to 20:80, and after dilution to a concentration of about 0.5 mass%, a softening agent (FS-8010, manufactured by Seiko PMC Corp., active ingredient 90 mass%) was added so that the active ingredient would be 0.3 mass% relative to the absolute dry mass of the pulp, and the same operation was performed except for this to obtain a pulp sheet for fluff pulp.

[0315] (Example 39)

[0316] In Example 34, after dilution to a concentration of about 0.5 mass%, a softening agent (FS-8010, manufactured by Seiko PMC Corp., active ingredient 90 mass%) was added so that the active ingredient would be 0.1 mass% relative to the absolute dry mass of the pulp, and the same operation was performed except for this to obtain a pulp sheet for fluff pulp.

[0317] (Example 40)

[0318] In Example 34, after dilution to a concentration of about 0.5 mass%, a softening agent (FS-8010, manufactured by Seiko PMC Corp., active ingredient 90 mass%) was added so that the active ingredient would be 0.3 mass% relative to the absolute dry mass of the pulp, and the same operation was performed except for this to obtain a pulp sheet for fluff pulp.

[0319] (Comparative Example 31)

[0320] In Example 31, the absolute dry mass ratio of bleached coniferous pulp to bleached broad-leaved pulp at the time of sheet formation was set to 100:0, and the same operation was performed except for this to obtain a pulp sheet for fluff pulp.

[0321] (Comparative Example 32)

[0322] In Example 31, after mixing the bleached coniferous pulp and the bleached broad-leaved pulp in a ratio of 20:80 by absolute dry mass, 20 g by absolute dry weight was taken and placed on a 80-mesh stainless steel sieve, and while applying a spray of ion-exchange water and stirring by hand, removal of fine fibers was performed. At this time, the amount of ion-exchange water was set to 20 L. The fine fibers that passed through the sieve together with the ion-exchange water were received with a 400-mesh stainless steel sieve. The obtained fine fibers were mixed with the pulp before removal of the fine fibers and supplied to sheet formation. The same operation as in Example 1 was performed except for this to obtain a pulp sheet for fluff pulp.

[0323] (Measurement and Evaluation)

[0324] [Amount of Fine Fibers]

[0325] The proportion of fine fibers contained in the fluff pulp board was calculated as follows. First, the fiber length of the pulp fibers in the fluff pulp board in the range of 0 to 7.60 mm was measured using a fiber analyzer (Valmet FS-5) according to JIS P 8226-2:2011. The number of fibers (ni) was measured for every 0.02 mm length range, and the length-weighted fiber length distribution was plotted. Based on Equation (2) described in JIS P 8226-2:2011, the percentage of the number of fibers weighted by the length range of 0 to 0.10 mm was calculated as the fine fiber content (%).

[0326] [ISO whiteness]

[0327] The determination was performed according to JIS P 8148:2018.

[0328] [Kappa value]

[0329] The determination was performed according to JIS P 8211:2011.

[0330] [Fibrinolytic]

[0331] The unwinding time (in seconds) was measured using the same method as described above for [unwinding property], and was used as an indicator for evaluating unwinding property.

[0332] [Making a Plush Mat]

[0333] Make the plush mat using the same method as described above for [making the plush mat].

[0334] [Determination of Backflow Rate of Plush Pads]

[0335] The backflow rate of the plush pad was determined using the same method as described above for [determination of the backflow rate of the plush pad].

[0336] [Determination of diaper backflow rate]

[0337] The backflow rate of diapers was measured entirely at 23°C and 50% relative humidity. First, test samples simulating diapers were prepared in the laboratory according to the following steps. Samples with a basis weight of 200 g / m² were prepared using the above method. 2 Press the plush mat with 2mm spacers between the layers for 10 minutes. The resulting 200g / m² mat... 2The pile mat was placed on a 5 mm thick acrylic plate so that the wire surface became the upper surface. After sandwiching a 2 mm thick spacer, another 5 mm thick acrylic plate was placed on top, and the whole was pressed for 10 minutes using a bench press. After the pressing was completed, the top acrylic plate was removed, and the pile mat was left to stand for 30 minutes. A stainless steel base plate (5 mm thick, 11 x 11 cm) was placed on a horizontal test bench, and the pile mat was placed on the base plate so that the wire surface became the upper surface. The high water-absorbent polymer (Aqua Keep SA60SXII, manufactured by Sumitomo Seika Co., Ltd.) was spread as evenly as possible on the pile mat at 140 g / m 2 The pile mat was placed on a 5 mm thick acrylic plate so that the wire surface became the upper surface. After sandwiching a 2 mm thick spacer, another 5 mm thick acrylic plate was placed on top, and the whole was pressed for 10 minutes using a bench press. After the pressing was completed, the top acrylic plate was removed, and the pile mat was left to stand for 30 minutes. A stainless steel base plate (5 mm thick, 11 x 11 cm) was placed on a horizontal test bench, and the pile mat was placed on the base plate so that the wire surface became the upper surface. The high water-absorbent polymer (Aqua Keep SA60SXII, manufactured by Sumitomo Seika Co., Ltd.) was spread as evenly as possible on the pile mat at 140 g / m 2 The pile mat was placed on a 5 mm thick acrylic plate so that the wire surface became the upper surface. After sandwiching a 2 mm thick spacer, another 5 mm thick acrylic plate was placed on top, and the whole was pressed for 10 minutes using a bench press. After the pressing was completed, the top acrylic plate was removed, and the pile mat was left to stand for 30 minutes. A stainless steel base plate (5 mm thick, 11 x 11 cm) was placed on a horizontal test bench, and the pile mat was placed on the base plate so that the wire surface became the upper surface. The high water-absorbent polymer (Aqua Keep SA60SXII, manufactured by Sumitomo Seika Co., Ltd.) was spread as evenly as possible on the pile mat at 140 g / m 2 The pile mat was placed on a 5 mm thick acrylic plate so that the wire surface became the upper surface. After sandwiching a 2 mm thick spacer, another 5 mm thick acrylic plate was placed on top, and the whole was pressed for 10 minutes using a bench press. After the pressing was completed, the top acrylic plate was removed, and the pile mat was left to stand for 30 minutes. A stainless steel base plate (5 mm thick, 11 x 11 cm) was placed on a horizontal test bench, and the pile mat was placed on the base plate so that the wire surface became the upper surface. The high water-absorbent polymer (Aqua Keep SA60SXII, manufactured by Sumitomo Seika Co., Ltd.) was spread as evenly as possible on the pile mat at 140 g / m 2 The pile mat was placed on a 5 mm thick acrylic plate so that the wire surface became the upper surface. After sandwiching a 2 mm thick spacer, another 5 mm thick acrylic plate was placed on top, and the whole was pressed for 10 minutes using a bench press. After the pressing was completed, the top acrylic plate was removed, and the pile mat was left to stand for 30 minutes. A stainless steel base plate (5 mm thick, 11 x 11 cm) was placed on a horizontal test bench, and the pile mat was placed on the base plate so that the wire surface became the upper surface. The high water-absorbent polymer (Aqua Keep SA60SXII, manufactured by Sumitomo Seika Co., Ltd.) was spread as evenly as possible on the pile mat at 140 g / m

[0338]

[0339] [Table 3]

[0340]

[0341] In the example, a pulp sheet for fluff pulp having good defibrability was obtained, and a fluff mat in which the backflow rate was suppressed was obtained, as compared with the comparative example.

[0342] (Example 41)

[0343] The bleached coniferous pulp after the D1 stage and the bleached broad-leaved pulp were mixed at a ratio of 0: 100 in terms of absolute dry mass, and after dilution with ion exchange water to a concentration of about 0.5 mass%, pulp sheeting was performed using a circular standard hand sheet machine (manufactured by Kumagai Riki Kogyo Co., Ltd.) so that the basis weight became 270 g / m2, and a pulp sheet for fluff pulp was obtained. 2

[0344] (Example 42)

[0345] In Example 41, the absolute dry mass ratio of the wood chips of Eucalyptus genus and the wood chips of Acacia genus (Acacia mangium) used in the preparation of the broad-leaved pulp was changed to 100:0, and the same operation was performed except for this, and a pulp sheet for fluff pulp was obtained.

[0346] (Example 43)

[0347] In Example 41, the absolute dry mass ratio of the wood chips of Eucalyptus genus and the wood chips of Acacia genus (Acacia mangium) used in the preparation of the broad-leaved pulp was changed to 0: 100, and the same operation was performed except for this, and a pulp sheet for fluff pulp was obtained.

[0348] (Example 44)

[0349] In Example 41, the absolute dry mass ratio of the bleached coniferous pulp and the bleached broad-leaved pulp at the time of sheeting was set to 20:80, and the same operation was performed except for this, and a pulp sheet for fluff pulp was obtained.

[0350] (Example 45)

[0351] In Example 41, the absolute dry mass ratio of the bleached coniferous pulp and the bleached broad-leaved pulp at the time of sheeting was set to 40:60, and the same operation was performed except for this, and a pulp sheet for fluff pulp was obtained.

[0352] (Example 46)

[0353] In Example 41, the absolute dry mass ratio of the bleached coniferous pulp and the bleached broad-leaved pulp at the time of sheeting was set to 60:40, and the same operation was performed except for this, and a pulp sheet for fluff pulp was obtained.

[0354] (Comparative Example 41) ​

[0355] In Example 41, the same operation was performed except that the absolute dry mass ratio of pine tree genus Pinus and genus Pseudotsuga was set to 100:0 and the absolute dry mass ratio of bleached pine tree pulp and bleached broadleaf tree pulp at the time of sheet making was set to 60:40, to obtain a pulp sheet for fluff pulp.

[0356] (Comparative Example 42)

[0357] In Example 44, the same operation was performed except that the absolute dry mass ratio of bleached pine tree pulp and bleached broadleaf tree pulp at the time of sheet making was set to 100:0, to obtain a pulp sheet for fluff pulp.

[0358] (Measurement and Evaluation)

[0359] [Length-weighted average fiber length]

[0360] Measurement of the disintegration average fiber length (length-weighted average fiber length) of the pulp fibers contained in the pulp sheet for fluff pulp was performed. The measurement of the length-weighted fiber length was performed using a fiber analyzer (FS-5 manufactured by Valmet Corporation) in accordance with JIS P 8226-2:2011.

[0361] [Fiber coarseness]

[0362] The measurement was performed using a fiber analyzer (FS-5 manufactured by Valmet Corporation) after disintegration of the pulp sheet for fluff pulp in accordance with JIS P 8220-1:2012.

[0363] [ISO whiteness]

[0364] The measurement was performed in accordance with JIS P 8148:2018.

[0365] [Kappa number]

[0366] The measurement was performed in accordance with JIS P 8211:2011.

[0367] [Fluffing of pulp]

[0368] The fluffing of the pulp was performed in an environment of 23°C and 50% relative humidity. The pulp sheet for fluff pulp, which was humidity-adjusted in an environment of 23°C and 50% relative humidity, was cut into 10 mm x 10 mm squares, 3 g was weighed, and was put into a Wonder blender (OSAKA CHEMICAL Co., Ltd., Model WB-1, rotation speed 25000 rpm) in a uniform manner. The defibration was performed for a prescribed time at intervals of 5 seconds, and after confirming the defibration time required for the un-defibrated matter to disappear, the pulp was made into a cotton shape at the defibration time. Hereinafter, the pulp made into a cotton shape by defibration is referred to as “fluff pulp”.

[0369] [Production of fluff pad]

[0370] Use at 23℃ and 50% relative humidity. Figure 1 The shown plush mat making apparatus 100 performs the making of plush mats. Here, the plush mat making apparatus 100 uses a pulp desiccant 5 (manufactured by Maruta Manufacturing Co., Ltd.), a stainless steel sieve 22 with a mesh size of 180μm (manufactured by AS ONE Co., Ltd., inner diameter 75mm × inner height 20mm), a stainless steel sieve 24 with a mesh size of 150μm (manufactured by AS ONE Co., Ltd., inner diameter 75mm × inner height 20mm), a column 20 made from a PET resin board cut into 70cm × 40cm pieces (manufactured by ACRYSUNDAY CO.,LTD., Sunday PET, thickness 0.5mm), a polypropylene powder funnel 10 (manufactured by AS ONE Co., Ltd., model No. 166, mouth diameter 180mm, foot outer diameter 43mm, foot length 48mm), a polypropylene powder funnel 30 (manufactured by AS ONE Co., Ltd., model No. 169, mouth diameter 120mm, foot outer diameter 30mm, foot length 27mm), and a household vacuum cleaner 40 (Hitachi Home & Life). Solution Corporation manufactured, model CV-CF4), assembled into Figure 1 The apparatus is configured as follows: First, the total weight of the 180μm mesh stainless steel sieve and column is measured beforehand. Next, the pulp defiberizer and a household vacuum cleaner are started. The vacuum cleaner is set to a low suction power (approximately 80W), and small amounts of fluff pulp (free of undefibered material) obtained from the [pulp fluffing] process are fed in at intervals from the top of the fluff pad forming device. The weight of the fluff pads formed on the 180μm mesh stainless steel sieve is measured occasionally, and fluff pad formation continues until 200g / m³ is reached. 2 Reaching 200g / m 2 Afterwards, stop the pulp defiber machine and the household vacuum cleaner. After removing the column, gently press the surface of the pile pad with a round stainless steel plate to adjust its shape, and gently remove the pile pad (75mm in diameter) from the 180μm mesh sieve without damaging its shape. The surface in contact with the stainless steel mesh is defined as the wire side of the pile pad.

[0371] [Density of the plush pad]

[0372] The density of the pile pad is calculated by measuring its basis weight and thickness. All procedures were performed at 23°C and 50% relative humidity. The density of the pile pad is calculated to be 200 g / m³. 2The batt was placed on a 5 mm-thick acrylic plate so that the wire surface became the upper surface. After a 2 mm-thick spacer was sandwiched, another 5 mm-thick acrylic plate was placed from above, and a table press was used for pressing for 10 minutes. After the pressing was completed, the placed acrylic plate was removed from above, and the sample was left to stand for 30 minutes. Next, the thickness was measured in such a manner that the wire surface of the batt faced upward, using a thickness gauge (Teclock Corporation, Model PG-14A, pressing load 0.394 N, measuring head diameter 16 mm) in accordance with the pressure prescribed in JIS L 1086:2007. Next, the weight of the produced batt having a diameter of 75 mm was measured using an electronic balance, and the basis weight was calculated.

[0373] [Measurement of the backflow rate of the batt]

[0374] The backflow rate of the batt was measured by the same method as in the above [Measurement of the backflow rate of the batt].

[0375] [Table 4]

[0376]

[0377] In the examples, a batt having a higher density (thinner thickness) and a suppressed backflow rate was obtained as compared with the comparative examples.

[0378] Explanation of Reference Signs

[0379] 5 Paper pulp defibrator

[0380] 10 Polypropylene powder hopper

[0381] 20 Column

[0382] 22, 24 Stainless steel screen

[0383] 30 Polypropylene powder hopper

[0384] 40 Dust collector (suction machine)

[0385] 22 Stainless steel screen with a mesh size of 180 μm

[0386] 100 Batt production device

Claims

1. A pulp board for fluff pulp, comprising hardwood pulp, the content of the hardwood pulp with respect to the total pulp components in the pulp board for fluff pulp is 25 mass% or more, the total content of straight-chain fatty acid having 24 carbon atoms, straight-chain fatty acid having 26 carbon atoms, and straight-chain fatty acid having 28 carbon atoms contained in the pulp board for fluff pulp is 300 to 1000 ppm.

2. The pulp board for fluff pulp according to claim 1, having ISO brightness of 80% or more as measured in accordance with JIS P 8148:2018.

3. The pulp board for fluff pulp according to claim 1, having viscosity of 7.0 to 15.0 mPa-s as measured in accordance with JIS P 8215:1998.

4. The pulp board for fluff pulp according to claim 1, wherein the kappa number of the hardwood pulp is 0.5 to 2.

0.

5. The pulp board for fluff pulp according to claim 1, wherein the content of the hardwood pulp with respect to the total pulp components in the pulp board for fluff pulp is 50 mass% or more.

6. The pulp board for fluff pulp according to claim 1, having kappa number of less than 1.5 as measured in accordance with JIS P 8211:2011.

7. A pulp board for fluff pulp, comprising hardwood pulp, the content of xylan contained in the pulp board for fluff pulp is 20 mass% or less, for a disintegrated pulp obtained by disintegrating the pulp board for fluff pulp in accordance with JIS P 8220-1:2012, Canadian Standard Freeness (CSF) becomes 400 to 640 mL when determined in accordance with JIS P 8121:2012-2.

8. The pulp board for fluff pulp according to claim 7, having ISO brightness of 82% or more as measured in accordance with JIS P 8148:2018.

9. The fluff pulp slurry board according to claim 7, wherein, in the case where the ISO brightness reduction rate is calculated from the ISO brightness of the pulp board for fluff pulp before and after heating at 105°C for 72 hours, the change amount of brightness becomes 5.0% or less when the ISO brightness is determined in accordance with JIS P 8154-1:2008, Change amount of ISO brightness (%) = B0 (%) - B1 (%) Here, B0 represents the ISO brightness of the pulp board for fluff pulp before the heating treatment, and B1 represents the ISO brightness of the pulp board for fluff pulp after the heating treatment.

10. The pulp board for fluff pulp according to claim 7, wherein the kappa number of the hardwood pulp is 0.3 to 2.

0.

11. The fluff pulp slurry board according to claim 7, wherein, the content of the hardwood pulp with respect to the total pulp components in the pulp board for fluff pulp is 25 mass% or more.

12. The pulp board for fluff pulp according to claim 7, having kappa number of less than 1.7 as measured in accordance with JIS P 8211:2011.

13. The pulp board for fluff pulp according to claim 7, having K value of less than 1.6 as measured in accordance with JIS P 8206:1982.

14. A pulp board for fluff pulp, comprising hardwood pulp, for the pulp fibers contained in the pulp board for fluff pulp, the proportion of the number of fibers weighted in the range of 0 to 0.1 mm in the length-weighted fiber length distribution is 10% or less when the length-weighted fiber length is determined in accordance with JIS P 8226-2:2011.

15. The pulp sheet for fluff pulp according to claim 14, having an ISO brightness of 82% or more as measured in accordance with JIS P 8148:2018.

16. The fluff pulp with pulp board according to claim 14, wherein, The kappa number of the hardwood pulp is 0.5 to 2.

0.

17. The pulp sheet for fluff pulp according to claim 14, having a kappa number of less than 1.7 as measured in accordance with JIS P 8211:2011.

18. The fluff pulp slurry board according to claim 14, wherein, The content of the hardwood pulp with respect to the total pulp components in the pulp sheet for fluff pulp is 25 mass% or more.

19. A pulp sheet for fluff pulp, comprising a hardwood pulp, The fiber coarseness of the pulp sheet for fluff pulp as measured by disintegration in accordance with JIS P 8220-1:2012 is 0.030 to 0.120 mg / m.

20. The fluff pulp with pulp board according to claim 19, wherein, The length-weighted average fiber length of the pulp fibers contained in the pulp sheet for fluff pulp as measured in accordance with JIS P 8226-2:2011 is 0.65 mm or more and less than 1.50 mm.

21. The pulp sheet for fluff pulp according to claim 19, having an ISO brightness of 82% or more as measured in accordance with JIS P 8148:2018.

22. The fluff pulp with pulp board according to claim 19, wherein, The kappa number of the hardwood pulp is 0.5 to 2.

0.

23. The fluff pulp with pulp board according to claim 19, wherein, The content of the hardwood pulp with respect to the total pulp components in the pulp sheet for fluff pulp is 25 mass% or more.

24. The pulp sheet for fluff pulp according to claim 19, having a kappa number of less than 1.7 as measured in accordance with JIS P 8211:2011.

25. A fluff pad formed from the pulp sheet for fluff pulp according to any one of claims 1 to 24.

26. The pile mat of claim 25 having a density of 0.058 g / cm 3 above.

27. An absorbent article provided with the fluff pad according to claim 25.

Citation Information

Patent Citations

  • Paper containing fluffed pulp

    JP2012211411A

  • Pulp sheet for fluff pulp

    WO2022138870A1